Poly (meth) acrylate impact modifiers with improved optical properties and methods for producing same

By controlling the amount of alkali metal ions in the emulsion polymer and adjusting the molar ratio of polyvalent metal ions, a combined aggregation method is used to solve the reduction in transparency of the poly(meth)acrylate molding composition after hot water storage and polymer separation. The problem is that high transparency and low wastewater concentration are achieved.

CN119137163APending Publication Date: 2024-12-13ROHM GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380036779.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-28
Filing Date
2023-04-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing poly(meth)acrylate molding compositions have reduced transparency after hot water storage, and the separation of polymers and aqueous phases leads to a high concentration of polymers in wastewater, increasing the wastewater treatment load.

Method used

By controlling the amount of alkali metal ions to less than or equal to 3.0 mmol/kg in the emulsion polymer and adjusting the molar ratio of alkali metal ions to less than or equal to 1.3, a combination of physical coagulation and chemical coagulation is performed by using a combination of physical coagulation and chemical coagulation Coagulation and dehydration reduce the amount of alkali metal ions in the polymer and improve the hot water storage stability of the polymer.

Benefits of technology

It significantly reduces the haze value after hot water storage, improves light transmittance, and reduces the polymer concentration in the wastewater, and reduces the wastewater treatment load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137163A_ABST
    Figure CN119137163A_ABST
Patent Text Reader

Abstract

The present invention relates to a poly (meth) acrylate impact modifier comprising at least one heterophasic alkyl (meth) acrylate emulsion polymer comprising at least one multivalent metal ion, for example selected from the group consisting of alkaline earth metals, zinc and aluminum, and a defined amount of alkali metal ions, wherein the impact modifier or the molding composition made therefrom has improved optical properties, in particular high transparency after storage in hot water. The impact modifier comprises less than or equal to 3.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier, and exhibits a molar ratio of alkali metal ions to multivalent metal ions of less than or equal to 1.3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer, comprising at least one polyvalent metal ion, for example selected from alkaline earth metals, zinc and aluminum, and a defined amount of alkali metal ions, wherein the impact modifier or a molding composition made therefrom has improved optical properties, in particular high transparency after hot water storage. The impact modifier comprises less than or equal to 3.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier, and exhibits a molar ratio of alkali metal ions to polyvalent metal ions of less than or equal to 1.3.

[0002] Furthermore, the present invention relates to a process for producing a poly(meth)acrylate impact modifier, which comprises preparing at least one multiphase alkyl(meth)acrylate polymer by emulsion polymerization, coagulation of the resulting latex and mechanical dehydration, wherein the amount of alkali metal ions and polyvalent metal ions, which usually originate from coagulants and other auxiliaries, in the dehydrated alkyl(meth)acrylate emulsion polymer is controlled.

[0003] The present invention also relates to impact-modified molding compositions, in particular impact-modified poly(methyl methacrylate) (PMMA) compositions, having an improved property profile, including good optical properties, in particular high transparency after hot water storage. The molding compositions are preferably used for producing molded articles and semi-finished products, such as films and sheets, in particular transparent articles and semi-finished products or products with good optical appearance. Background Art

[0004] It is known that the impact resistance of molding compositions, especially relatively brittle synthetic resins, such as poly(meth)acrylate molding compositions, can be improved by incorporating appropriate amounts of so-called impact modifiers. It has become an industry practice to use impact modifiers known as core particles, core-shell particles or core-shell-shell particles made by emulsion polymerization. These typically include an elastomeric phase (e.g. as a core or as an intermediate shell grafted onto the core) and a hard outer phase (which typically ensures that the impact modifier particles are well incorporated into the matrix polymer). Such multiphase emulsion polymers and their preparation are described, for example, in WO 2004 / 056893.

[0005] Typically, such impact modifiers made by emulsion graft polymerization are obtained as aqueous polymer dispersions (latexes) which require post-treatment by coagulation and separation of the emulsion polymer.Several coagulation (also called precipitation) processes of polymer latexes are known and described in the prior art.

[0006] In general, it is described that emulsion polymers, such as the poly(meth)acrylate impact modifiers of the present invention, can be coagulated by means of known physical coagulation methods, such as shear coagulation, hot shear coagulation, spray drying, freeze coagulation or pressure coagulation methods, or by means of chemical coagulation methods, which include the addition of electrolytes, in particular polyvalent cations, such as alkaline earth metal salts, aluminum salts or zinc salts, or inorganic or organic acids.

[0007] For example, WO 2015 / 074883 describes the coagulation of aqueous polymer dispersions by means of continuous or semi-continuous freeze coagulation and subsequent mechanical dehydration (e.g. using a centrifugation step). Coagulation and dehydration of emulsion polymers coagulated via thermal shear in an extruder line are described, for example, in WO 02 / 184539, EP 0 683028 and EP 0 187 715. In EP 0 467 288, it is described that acrylic molded products comprising acrylic polymer freeze coagulated materials exhibit better extrusion stability than coagulated materials obtained by spray drying or using common chemical coagulants such as aluminum chloride, sodium chloride, magnesium sulfate or sulfuric acid.

[0008] In general, the coagulation and dewatering processes of emulsion polymers, especially in extruder systems, suffer from the problem that the separated aqueous phase often has an undesirably high polymer concentration. This constitutes a particular disadvantage since it leads to high loads (chemical oxygen demand (COD value)) on the clarification equipment and losses of polymer product in the wastewater treatment process. It is therefore desirable to provide an improved process which leads to a reduced polymer concentration in the separated aqueous phase and in the wastewater.

[0009] Another common way for the coagulation of emulsion polymers is to mix the emulsion polymer (latex) with a coagulant, which is usually selected from aqueous solutions of metal salts (especially divalent or trivalent metal ions) and / or acids (such as sulfuric acid, acetic acid, phosphorous acid). For example, aqueous solutions of alkali metal salts, alkaline earth metal salts, zinc salts or aluminum salts, such as magnesium sulfate, calcium chloride and aluminum chloride, are used as coagulants.

[0010] Document JPH03247603 describes a method for coagulating a latex of a grafted polymer, wherein the latex and a conventional coagulant are mixed with a co-rotating twin-screw kneader. The coagulant can be selected, for example, from sodium chloride, calcium chloride, magnesium chloride, sodium sulfate, magnesium sulfate, several carbonates, aluminum salts and acids. The coagulant can be added to the method in an amount of 0.05 to 50% by weight based on the solid content of the polymer latex. The latex polymer can be, for example, a graft copolymer of butyl acrylate grafted with methyl methacrylate. The amount of alkali metal ions or alkaline earth metal ions in the dehydrated grafted polymer is not mentioned in JPH03247603.

[0011] Document JP 2000-119476 describes an acrylic multilayer structure polymer obtained by coagulating an emulsion polymer latex using a coagulant, wherein the residual amount of cations derived from the coagulant is not more than 200ppm. The coagulant is usually one selected from magnesium sulfate, calcium chloride and aluminum sulfate. Usually, coagulation is achieved by mixing the emulsion polymer latex with an aqueous solution of magnesium sulfate, calcium chloride or aluminum sulfate. The acrylic multilayer structure polymer consists of a hard outer layer containing methacrylate units and a soft inner layer containing acrylate units. Known anionic surfactants can be used in the emulsion polymerization of the acrylic multilayer structure polymer, such as sodium stearate, sodium myristate, sodium dioctyl sulfosuccinate, sodium dodecylbenzene sulfonate, sodium dodecylbenzene sulfonate, sodium lauryl sulfate. JP 2000-119476 describes washing the coagulated polymer until the required amount of magnesium or calcium ions is obtained. There is no mention of the amount of alkali metal ions or the ratio of alkali metal ions to alkaline earth metal ions in JP 2000-119476.

[0012] Document JP 2005-171141 describes a latex with improved dehydration behavior, which contains a multilayer structure polymer suitable for a modifier, film or molding material. The latex of JP 2005-171141 has a solid content of 35 to 42% by weight, and the multilayer polymer particles in the latex show a mass average particle diameter of 0.100-0.770 μm. In addition, JP 2005-171141 describes a method for coagulating and covering multilayer polymers from the latex, wherein coagulation is achieved by contacting the latex with a coagulant, such as sulfuric acid, hydrochloric acid, calcium chloride, magnesium sulfate, calcium formate and calcium acetate. In addition, buffers are mentioned, including the addition of alkali metals or alkaline earth metals. For example, based on the solid content of 100 parts by mass of the multilayer polymer latex, calcium acetate is added as a coagulant in an amount of 1.0 to 4.0% by mass. Scale formation (ie calcium carbonate deposition) was determined by filtering the multilayer polymer latex through a 150 μm metal mesh and collecting the scale from the inner wall of the polymerization reactor.The amount of alkali metal salt or alkaline earth metal salt in the dehydrated polymer or the final polymer product is not mentioned in JP 2005-171141.

[0013] Document EP 0 187 715 describes a method for coagulating an aqueous polymer latex by contacting the aqueous polymer latex with an aqueous solution of a water-soluble, non-nucleophilic, non-oxidizing alkaline earth metal and / or zinc salt and recovering the coagulated polymer. The coagulant is used in an effective amount of 0.05 to 5% by weight, based on the weight of the latex polymer solids. For example, calcium acetate or calcium hypophosphite is used as a coagulant. For example, the polymer latex is contacted with the coagulant in an extruder comprising a coagulation zone, a dehydration zone and a devolatilization zone. It is described that the water haze value, the yellowness index and the light transmittance can be improved by the method of EP 0 187 715. The amount of alkali metal salt or alkaline earth metal salt in the dehydrated polymer or the final polymer product is not mentioned in EP 0 187 715.

[0014] Document EP 0 465 049 describes blends of poly(methyl methacrylate) and heterogeneous core / shell polymers having an alkyl acrylate polymer grade and an alkyl methacrylate polymer shell, wherein the color of the polymer blend can be improved when the core / shell polymer is treated with a phosphorus-containing reducing agent. In particular, EP 0 465 049 discloses the addition of sodium hypophosphite or calcium hypophosphite to the emulsion polymer prior to coagulation by freeze drying or spray drying. For example, the hypophosphite reducing agent is added in an amount of 0.025 to 0.10% on a solids / solids basis. However, the amount of alkali metal salts or alkaline earth metal salts in the dewatering polymer or the final impact modifier is not mentioned in these examples. Furthermore, EP 0 465 049 describes dry blending of PMMA matrix polymer, impact modifier powder and sodium hypophosphite, wherein the amount of sodium hypophosphite (NaH2PO2) is 50 to 200 ppm, based on the polymer blend (matrix polymer / impact modifier=1:1).

[0015] Document EP 2 189 497 A1 relates to polymer compositions comprising a multistage copolymer, a phosphate of a polyvalent cation, which is added in particular for the coagulation of the multistage copolymer latex, and more than 100 ppm of an alkaline phosphate, calculated as phosphorus, based on the dry multistage copolymer. In particular, EP 2 189 497 A1 describes the preparation and coagulation of a multistage graft copolymer having a crosslinked butadiene / styrene core, wherein the coagulated and washed multistage graft copolymer is treated with disodium hydrogen phosphate (Na2HPO4), and wherein the disodium hydrogen phosphate is added in excess relative to the calcium ions, so that no calcium chloride remains and all calcium ions are present in the form of calcium phosphate. After the treatment, the multistage graft copolymer is dried and incorporated as an impact modifier in an amount of 5% by weight into a polycarbonate molding composition. As a result, the multistage copolymer contains a large amount of sodium ions.

[0016] Document EP 3 747 914 A1 describes a multilayer acrylic polymer coacervate characterized by its bulk density, particle diameter, wherein the amount N of alkali metal and alkaline earth metal (in mmol / kg) is defined based on the glass transition temperature Tg (in ° C.) of the acetone solubles of the coacervate and the valence a of the alkali metal and alkaline earth metal by the formula ∑(N / a)*(120-Tg)≤100. The multilayer acrylic polymer coacervate of D1 is said to exhibit excellent transparency, hot water whitening resistance and stress whitening resistance.

[0017] Document EP 2 942 360 describes a thermoplastic resin powder obtained by coagulating a polymer latex made by emulsion polymerization using a phosphoric acid ester as an emulsifier, wherein the free acid content in the resin is not more than 500 ppm. EP 2 942 360 describes that the presence of polyvalent metal ions in the thermoplastic resin powder leads to a reduction in the fluidity of the thermoplastic resin powder, and therefore the amount of coagulant should be as small as possible. It is described that the thermoplastic resin powder contains less than 50 ppm of calcium, preferably less than 50 ppm of calcium and magnesium combined, and 60 to 300 ppm of aluminum and more than 50 ppm of phosphorus. For example, aluminum sulfate or sulfuric acid is used as a coagulant. The amount of alkali metal ions is not discussed in EP 2 942 360.

[0018] Document GB 2 226 324 A describes a transparent, viscous molding composition comprising 10 to 90% of a hard phase made of methyl methacrylate and 1 to 90% of a viscous phase, for example made of a crosslinked butyl acrylate polymer, distributed in the hard phase, wherein the molding composition contains not more than 0.05% by weight of water-soluble components. It is described that the aqueous phase is separated from the coagulant in liquid form to such an extent that not more than 0.05% by weight of water-soluble components remain in the composition in order to ensure permanent clarity, in particular under the action of moisture.

[0019] Document WO 2013 / 160029 describes a polymer composition containing at least a graft polymer B1 made by emulsion polymerization and an optional thermoplastic polymer A, a rubber-free vinyl (co)polymer and other polymers or polymer additives. The emulsion graft copolymer is precipitated with at least one alkaline earth metal salt in an alkaline medium, and the copolymer contains at least one sodium salt and at least one alkaline earth metal salt with a molar ratio Na / (Mg+Ca) of at least 0.10 and at most 1.0. It is described that the molded article prepared from the emulsion graft copolymer B1 should have improved surface quality after storage under warm-humidity conditions. WO 2013 / 160029 teaches reducing the amount of alkaline earth metal salts derived from coagulants by adding sodium salts, such as sodium phosphate, during the emulsion polymerization and / or coagulation process, and if necessary, increasing the amount of sodium. The examples of WO 2013 / 160029 disclose a pre-compound of 50 wt% acrylonitrile / butadiene / styrene (ABS) emulsion graft copolymer and a thermoplastic styrene / acrylonitrile copolymer (SAN), wherein the ABS emulsion graft copolymer contains potassium ions in an amount of 130 or 100 ppm and sodium ions in an amount of 35 or 110 ppm. WO 2013 / 160029 does not describe an emulsion graft copolymer having an alkali metal ion content of less than 3 mmol / kg.

[0020] Particularly important properties of impact-modified PMMA molding compositions are favorable mechanical properties, such as high toughness (impact resistance, notched impact resistance), high elasticity (elastic modulus) as well as good processability (thermoplastic flowability, MVR) and good weathering and heat resistance. In addition, a fundamental requirement for PMMA molding compositions and articles is optical transparency even at elevated temperatures or after exposure to hot water. Generally, optically transparent products are those having a haze value of less than or equal to 15.0%, in particular below 10.0%, very particularly below 6.0%, measured at 23° C. on a test specimen with a thickness of 1 mm according to standard ASTM D1003 (2013) with the aid of a BYK Gardner Hazegard-plus haze meter.

[0021] Generally, the problem is that impact-modified PMMA molding compositions and articles made therefrom exhibit reduced transparency and become milky after storage in hot water, in particular in water at 80° C. for 10 to 24 hours. Therefore, it is highly desirable to provide impact-modified PMMA molding compositions that exhibit reduced haze and high light transmittance after storage in hot water. Summary of the invention

[0022] Purpose of the Invention

[0023] An object of the present invention is to provide a poly(meth)acrylate impact modifier, and a molding composition, a molding and a semi-finished product, such as a film and a sheet, comprising the poly(meth)acrylate impact modifier, which has improved optical properties, in particular high transparency and high transmittance. In particular, the impact modifier should lead to lower haze values ​​measured according to standard ASTM D1003 (2013) at 23° C. for a test specimen with a thickness of 1 mm, compared to the prior art modifiers, in particular after hot water storage at 70° C. and 80° C. In addition, the impact modifier should exhibit high transmittance values ​​even after hot water storage at 70° C.-80° C., for example, for 4-24 hours. In particular, an object of the present invention is to obtain a semi-finished product, preferably a transparent semi-finished product, which has an ASTM 1003-13 haze of <30%, preferably <20%, after hot water storage at 70° C., preferably after hot water storage at 80° C., for example, for 4-24 hours.

[0024] Another object of the present invention is to provide a cost-effective and easy process for producing poly(meth)acrylate impact modifiers and / or impact-modified polymer compositions. In particular, it is an object of the present invention to facilitate and optimize the separation of polymer from the aqueous phase, wherein the polymer content in the wastewater from the dewatering is reduced.

[0025] Solution according to the invention

[0026] Surprisingly, it was found that when the amount of alkali metal ions in the impact modifier, especially after coagulation and dehydration, is reduced to or below a critical value of about 3.0 mmol / kg, preferably 2.5 mmol / kg, more preferably below 2.0 mmol / kg based on dry impact modifier and at the same time the molar ratio of alkali metal ions to polyvalent metal ions, preferably selected from alkaline earth metals, zinc and aluminum, is adjusted to less than or equal to 1.3, preferably less than or equal to 1.2, the haze of the impact modifier or transparent articles made therefrom after hot water storage is reduced. In addition, in general, the impact modifier of the present invention or a sample containing the same shows high transmittance values ​​even after hot water storage.

[0027] Typically, the alkali metal ions come from additives used in the emulsion polymerization, such as emulsifiers, initiators and buffers. Typically, the salt content in the condensed polymer can be reduced by washing and / or by a higher degree of dehydration. Surprisingly, it has been found that such a desired low amount of alkali metal ions can be obtained by adding a polyvalent metal ion salt, such as an alkaline earth metal salt (e.g. calcium acetate or calcium hydroxide) or an aluminum salt before or during the condensation rather than after the condensation. In particular, it has been found that a combination of a specified maximum amount of alkali metal ions and a minimum amount of polyvalent metal ions (such as alkaline earth metal ions or aluminum ions) that are usually added before the emulsion polymer condenses improves the hot water storage stability of the impact modifier. In addition, a preferred minimum amount of polyvalent metal ions greater than or equal to 0.5 mmol / kg, preferably 2.0 mmol / kg, is advantageous.

[0028] Furthermore, it has been found that if specific values ​​of alkali metal ions in the dewatering polymer and the molar ratio of alkali metal ions to polyvalent metal ions are met, the amount of polymer in the wastewater formed from the separated aqueous phase is significantly reduced.

[0029] Description of the invention

[0030] The present invention relates to a poly(meth)acrylate impact modifier (hereinafter also referred to as impact modifier), comprising (preferably essentially consisting of) at least one multiphase alkyl(meth)acrylate emulsion polymer (hereinafter also referred to as emulsion polymer), wherein the poly(meth)acrylate impact modifier comprises at least one multivalent metal ion and less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg, more preferably less than or equal to 2.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier, and wherein (in the poly(meth)acrylate impact modifier) ​​the molar ratio of alkali metal ions to multivalent metal ions, preferably selected from alkaline earth metals, zinc and aluminum, is less than or equal to 1.3, preferably less than or equal to 1.2.

[0031] Typically, the metal ions contained in the impact modifier of the present invention come from the adjuvants used in the emulsion polymerization process of the multiphase (meth) alkyl acrylate emulsion polymer, such as initiators, surfactants and buffer salts. Typically, a significant amount of the metal ions in the impact modifier comes from the coagulant used to separate the emulsion polymer from the aqueous latex dispersion. In addition, the metal ions can come from additives added to the impact modifier, such as stabilizers. In particular, the alkali metal ions contained in the impact modifier of the present invention come from the initiator and / or surfactant used in the emulsion polymerization. In particular, the multivalent ions contained in the impact modifier of the present invention, such as alkaline earth metal ions, come from a coagulant containing a salt of at least one multivalent metal ion, such as an alkaline earth metal salt, added before coagulation.

[0032] The term "polyvalent metal" or "polyvalent metal ion" relates to a metal ion having two or more, preferably two or three, ionic charges. Preferably, the polyvalent metal ion may be selected from metals of IUPAC Group 2 (alkaline earth metals) and IUPAC Groups 8 to 14, more preferably selected from metals of IUPAC Group 2 (alkaline earth metals), IUPAC Group 12 (zinc group) and IUPAC Group 13 (boron group).

[0033] The term "alkali metal" or "alkali metal ion" includes elements of IUPAC Group 1 of the Periodic Table, in particular lithium (Li), sodium (Na) and potassium (K). The term "alkaline earth metal" or "alkaline earth metal ion" includes elements of IUPAC Group 2 of the Periodic Table, in particular magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba).

[0034] As used herein, the term "(meth)acrylate" is intended to encompass methacrylates, acrylates, and mixtures thereof.

[0035] The term "alkyl (meth)acrylate polymer" refers to a polymer comprising at least 30 wt%, preferably at least 40 wt%, more preferably at least 50 wt% of alkyl (meth)acrylate monomer units, and includes copolymers of alkyl (meth)acrylate monomers and one or more other copolymerizable monomers.

[0036] The term "alkyl (meth)acrylate emulsion polymer" refers to a multiphase emulsion polymer comprising at least 30 weight percent, preferably at least 40 weight percent, and more preferably at least 50 weight percent of alkyl (meth)acrylate monomer units in the shell, wherein the shell may include a copolymer of an alkyl (meth)acrylate monomer and one or more other copolymerizable monomers (e.g., styrene).

[0037] The term "aqueous" or "aqueous solution" means that the medium or solvent consists of water or contains water as a major component. For example, a polar water-miscible co-solvent, such as an alcohol, may be included in the medium or solvent.

[0038] The term "latex" as used in connection with the present invention refers to a water-insoluble polymer which is dispersed in an aqueous phase, preferably stabilized by one or more surfactants, and which is prepared by conventional polymerization techniques, preferably by emulsion polymerization.

[0039] If not defined otherwise, according to the present invention, the term ppm refers to mg / kg. For example, the term ppm refers to mg / kg based on the solids content of the poly(meth)acrylate impact modifier.

[0040] The content of metal ions, for example alkali metals, and polyvalent metal ions, for example alkaline earth metals in the emulsion polymer or impact modifier is usually determined by atomic emission spectrometry after chemical digestion of the polymer sample, for example microwave-assisted digestion of the polymer sample in nitric acid. The amount of alkali metals and polyvalent metals, for example alkaline earth metals or aluminum is usually given taking into account the detection limit of the respective analytical method. For example, an amount given in 0% by weight or 0 mmol / kg is understood to be below the detection limit of the respective analytical method.

[0041] Preferably, the at least one polyvalent metal ion is selected from metal ions of IUPAC Group 2 (alkaline earth metals), IUPAC Group 12 (zinc group) and IUPAC Group 13 (boron group). More preferably, the polyvalent metal ion is selected from alkaline earth metals, preferably magnesium (Mg) and / or calcium (Ca), and metals of IUPAC Group 13, preferably aluminum. Most preferably, the polyvalent metal ion is selected from alkaline earth metals, zinc (Zn) and aluminum (Al). In a further preferred embodiment, the at least one polyvalent metal ion is selected from magnesium (Mg), calcium (Ca), zinc (Zn) and aluminum (Al), more preferably selected from magnesium (Mg), calcium (Ca) and aluminum (Al).

[0042] In a preferred embodiment, the alkali metal ions are selected from sodium and potassium ions, and the at least one multivalent ion is selected from alkaline earth metals, aluminum and zinc, more preferably from calcium, magnesium and aluminum.

[0043] In particular, the amount of alkali metal ions relates to the sum of all alkali metal ions present in the poly(meth)acrylate impact modifier. In particular, the amount of polyvalent metal ions, such as alkaline earth metal ions and / or aluminum ions relates to the sum of all polyvalent metal ions, such as alkaline earth metal ions and / or aluminum ions present in the poly(meth)acrylate impact modifier. Preferably, the alkali metal ions are sodium ions and / or potassium ions, and the amount of alkali metal ions relates to the sum of sodium ions and potassium ions. Preferably, the polyvalent metal ions are magnesium ions, calcium ions and / or aluminum ions, and the amount of polyvalent metal ions relates to the sum of magnesium ions, calcium ions and aluminum ions.

[0044] The at least one alkali metal ion and the at least one multivalent metal ion, such as an alkaline earth metal ion or an aluminum ion, can be present in the impact modifier in any arbitrary form, such as in the form of a solid salt or salt inclusions, which are dissolved in the aqueous phase, bound to or adsorbed to other components or groups of the emulsion polymer, such as anionic groups.

[0045] Preferably, the poly(meth)acrylate impact modifier comprises 0 to 3.0 mmol / kg, preferably 0 to 2.5 mmol / kg, more preferably 0 to 2 mmol / kg, further preferably 0.01 to 3.0 mmol / kg, further preferably 0.01 to 2.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier.

[0046] Preferably, the poly(meth)acrylate impact modifier contains 0.5 to 20.0 mmol / kg, preferably 1.0 to 10.0 mmol / kg, more preferably 2.0 to 8.0 mmol / kg of polyvalent metal ions, such as alkaline earth metal ions and / or aluminum ions, based on the solid content of the impact modifier.

[0047] Preferably, the poly(meth)acrylate impact modifier comprises less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg, of alkali metal ions, based on the solid content of the impact modifier; and greater than or equal to 0.5 mmol / kg, preferably greater than or equal to 1.0 mmol / kg, more preferably greater than or equal to 2.0 mmol / kg, and further preferably greater than or equal to 3.0 mmol / kg, of at least one multivalent metal ion, based on the solid content of the impact modifier.

[0048] In a particularly preferred embodiment, the poly(meth)acrylate impact modifier comprises 0 to 3.0 mmol / kg, preferably 0 to 2.5 mmol / kg, further preferably 0.01 to 3.0 mmol / kg, particularly preferably 0.1 to 2.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier, and 0.5 to 20.0 mmol / kg, preferably 1.0 to 10.0 mmol / kg, more preferably 2.0 to 8.0 mmol / kg of polyvalent metal ions, for example alkaline earth metal ions and / or aluminum ions, based on the solids content of the poly(meth)acrylate impact modifier.

[0049] In the impact modifier of the present invention, the molar ratio of alkali metal ions to polyvalent ions (e.g., alkaline earth metal ions and / or aluminum ions) is less than or equal to 1.3; preferably less than or equal to 1.2; preferably less than or equal to 1.0; more preferably less than or equal to 0.8, more preferably less than or equal to 0.7. Particularly preferably, the molar ratio of alkali metal ions to polyvalent ions (e.g., alkaline earth metal ions and / or aluminum ions) is in the range of 0 to 1.3, further preferably in the range of 0.01 to 1.3, more preferably in the range of 0.1 to 1.3.

[0050] In particular, in the impact modifier of the present invention, the molar ratio of polyvalent ions (e.g., alkaline earth metal ions and / or aluminum ions) to alkali metal ions is greater than or equal to 0.8, preferably greater than or equal to 0.9, further preferably greater than or equal to 1.0, more preferably greater than or equal to 2.0. Particularly preferably, the molar ratio of polyvalent ions (e.g., alkaline earth metal ions and / or aluminum ions) to alkali metal ions is in the range of 0.8 to 20, preferably in the range of 0.9 to 10.

[0051] In a preferred embodiment, the poly(meth)acrylate impact modifier comprises less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg, and more preferably less than or equal to 2.0 mmol / kg of sodium and / or potassium ions, based on the solid content of the impact modifier; and greater than or equal to 1.0 mmol / kg, preferably greater than or equal to 2.0 mmol / kg, and more preferably greater than or equal to 3.0 mmol / kg of magnesium, calcium and / or aluminum ions, based on the solid content of the impact modifier. Typically, this amount refers to the sum of the alkali metal ions present in the impact modifier or the sum of the magnesium, calcium and / or aluminum ions.

[0052] Typically, the impact modifier comprises or consists essentially of polymer particles prepared by emulsion polymerization. After the emulsion polymerization, the impact modifier is in the form of an aqueous polymer dispersion at the end of the synthesis step. Such an aqueous polymer dispersion is also called latex and contains not only the polymer fraction but also polar water-soluble auxiliary materials required for carrying out the polymerization step, such as surfactants, buffer substances, initiators and other redox components.

[0053] Multiphase alkyl (meth)acrylate emulsion polymer

[0054] Preferably, the multiphase alkyl (meth)acrylate emulsion polymer is an emulsion polymer obtained by emulsion polymerization, preferably by sequential emulsion polymerization of alkyl (meth)acrylate monomers and optionally other copolymerizable monomers, wherein the emulsion polymer has a multiphase structure comprising at least one core and at least one shell, preferably one or two shells.

[0055] For example, a multiphase (meth) alkyl acrylate emulsion polymer can be formed from crosslinked particles having a core-shell structure or a core-shell-shell structure. Typically, the particles have an average particle diameter between 20 nm and 500 nm, preferably between 50 nm and 450 nm, more preferably between 100 nm and 400 nm, and most preferably between 150 nm and 350 nm. The average particle diameter can be determined by methods known to those skilled in the art, for example by static or dynamic light scattering, such as laser diffraction measurements or photon correlation spectroscopy according to DIN ISO 13321:1996. Typically, the volume average particle diameter can be obtained by light scattering measurements.

[0056] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer comprises a soft elastomeric core and a hard non-elastomeric outer phase, which is usually prepared by graft emulsion polymerization in the presence of the core. The multiphase alkyl (meth)acrylate emulsion polymer is hereinafter referred to as a core-shell emulsion polymer. For example, the soft elastomeric core can be based on polybutadiene or crosslinked acrylic C1-C 10 Alkyl ester polymers, such as cross-linked polybutyl acrylate.

[0057] In another preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer comprises a hard non-elastomeric core; a soft elastomeric intermediate shell, typically made by graft emulsion polymerization in the presence of the core, and a hard non-elastomeric outer shell, typically made by graft emulsion polymerization in the presence of the intermediate core-shell particles. The multiphase alkyl (meth)acrylate emulsion polymer is hereinafter referred to as a core-shell-shell emulsion polymer.

[0058] Preferably, the outer shell of the multiphase emulsion polymer is a hard phase comprising at least 70 wt %, more preferably at least 80 wt %, based on the outer shell, of at least one C1-C6 alkyl methacrylate, preferably at least 70 wt %, more preferably at least 80 wt %, based on the outer shell, of methyl methacrylate.

[0059] Preferably, at least 50 wt. %, more preferably at least 55 wt. %, more preferably at least 80 wt. %, of the outer layer, based on the total weight of the emulsion polymer, is covalently bonded to the soft phase, i.e. the soft core of a core-shell emulsion polymer or the intermediate shell of a core-shell-shell emulsion polymer. Typically, the amount of covalently bonded outer layer (grafted polymer) (or also referred to as degree of grafting) is determined as the amount of acetone insolubles.

[0060] In order to determine the degree of grafting, the water of the emulsion polymer dispersion is removed in a drying oven to obtain the solid content of the pure modifier. 1.5 grams of the multiphase emulsion polymer is mixed with 40 grams of acetone and stirred at 40°C until a turbid solution is obtained (2-3 hours). The insoluble grafted polymer is separated by centrifugation (e.g. 9000rpm, 2-5 hours), and the clear supernatant is dried to constant weight to obtain the amount of the soluble fraction. The degree of grafting is then calculated using formula (1).

[0061] Grafting degree = 100% - acetone soluble content (1)

[0062] Preferably, the degree of grafting of the emulsion polymer is in the range from 50 to 100% by weight, preferably from 52 to 99% by weight, based on the solids content of the emulsion polymer.

[0063] Preferably, the alkyl (meth)acrylate emulsion polymer comprises at least 60% by weight, preferably at least 75% by weight, based on the total emulsion polymer, of at least one C1-C1 (meth)acrylate. 20 Alkyl esters, more preferably methyl methacrylate and / or n-butyl acrylate.

[0064] Typically, (meth)acrylates include (meth)acrylic acid C1-C 10 -alkyl esters, (meth) acrylic acid C2-C 20 -Alkenyl ester, (meth) acrylic acid C6-C 20 Aryl ester, (meth) acrylic acid C6-C 20 Aryl alkyl esters, (meth) acrylic acid C1-C 10 Hydroxyalkyl esters, glycol di(meth)acrylates and multifunctional (meth)acrylates.

[0065] Preferably, the emulsion polymer comprises at least one methacrylic acid C1-C 10 Alkyl esters, which are preferably selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, isooctyl methacrylate and ethylhexyl methacrylate, and cycloalkyl methacrylates, such as cyclohexyl methacrylate.

[0066] Preferably, the emulsion polymer comprises at least one acrylic acid C1-C 10 Alkyl esters which are preferably selected from methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, isooctyl acrylate and ethylhexyl acrylate, and cycloalkyl acrylates such as cyclohexyl acrylate.

[0067] In particular, the multiphase alkyl (meth)acrylate emulsion polymer comprises (preferably consists of):

[0068] At least 10% by weight, preferably at least 20% by weight, preferably from 10 to 70% by weight of at least one methacrylic acid C1-C 10 , preferably C1-C6 alkyl ester, preferably methyl methacrylate;

[0069] 5 to 80% by weight, preferably 20 to 80% by weight, of at least one acrylic acid C1-C 10 an alkyl ester (preferably n-butyl acrylate) or at least one conjugated diene (preferably butadiene);

[0070] 0 to 2 wt. %, preferably 0.1 to 2 wt. %, more preferably 0.5 to 1 wt. % of at least one crosslinking monomer, preferably a multifunctional (meth)acrylate and / or allyl (meth)acrylate; and

[0071] 0 to 15% by weight, preferably 0.5 to 10% by weight, more preferably 0.5 to 5% by weight, of optional additional monomers, preferably different from the abovementioned monomers, for example vinyl aromatic monomers, such as styrene, α-methylstyrene or benzyl methacrylate, preferably styrene.

[0072] The amounts are given based on the total mass of the monomers.

[0073] More particularly, the multiphase alkyl (meth)acrylate emulsion polymer comprises (preferably consists of):

[0074] At least 40% by weight, preferably 40 to 70% by weight, of at least one methacrylic acid C1-C 10 , preferably C1-C6 alkyl ester, preferably methyl methacrylate;

[0075] 5 to 45% by weight, preferably 20 to 45% by weight, preferably 25 to 42% by weight of at least one acrylic acid C1-C 10 Alkyl ester, preferably C1-C6 alkyl acrylate, preferably selected from ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate and butyl methacrylate, more preferably, C1-C6 alkyl acrylate 10 Alkyl esters include n-butyl acrylate;

[0076] 0 to 2 wt. %, preferably 0.1 to 2 wt. %, more preferably 0.5 to 1 wt. % of at least one crosslinking monomer, preferably a multifunctional (meth)acrylate and / or allyl (meth)acrylate; and

[0077] 0 to 15 wt. %, preferably 0 to 12 wt. %, more preferably 0.5 to 10 wt. % of optional additional monomers, preferably different from the abovementioned monomers, for example vinyl aromatic monomers, such as styrene, benzyl methacrylate.

[0078] The amounts are given based on the total mass of the monomers.

[0079] Preferably, the multiphase alkyl (meth)acrylate emulsion polymer comprises vinyl aromatic monomers such as styrene and / or C7-C8 (meth)acrylate. 20Arylalkyl esters, such as benzyl methacrylate, are used to adjust the refractive index difference between the hard phase and the soft phase. Styrenes that can be used are styrene, substituted styrenes having alkyl substituents in the side chains, such as α-methylstyrene and α-ethylstyrene, substituted styrenes having alkyl substituents on the rings, such as vinyltoluene and p-methylstyrene, and halogenated styrenes, such as monochlorostyrene, dichlorostyrene, tribromostyrene, and tetrabromostyrene.

[0080] Typically, the crosslinking monomer has two or more polymerizable double bonds in the molecule. The crosslinking monomer may be selected from difunctional (meth)acrylates, trifunctional or polyfunctional (meth)acrylates and other known crosslinking agents such as allyl methacrylate, allyl acrylate and divinylbenzene.

[0081] For example, difunctional (meth)acrylates are diesters of (meth)acrylic acid and polyfunctional alcohols, such as di(meth)acrylates of propylene glycol, butylene glycol, hexylene glycol, octanediol, nonanediol, decanediol, eicosandiol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dodecaethylene glycol, tetradecaethylene glycol, propylene glycol, dipropylene glycol, tetradecapropylene glycol. For example, trifunctional or polyfunctional (meth)acrylates are triesters or polyesters of (meth)acrylic acid and polyfunctional alcohols, such as trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate.

[0082] Suitable crosslinking monomers are described, for example, in WO 02 / 20634 and EP 0 522 351.

[0083] Preferably, the alkyl (meth)acrylate emulsion polymer comprises at least one crosslinking monomer selected from ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, divinylbenzene and allyl (meth)acrylate. More preferably, the crosslinking monomer is allyl methacrylate.

[0084] The alkyl (meth)acrylate emulsion polymer may contain 0 to 15% by weight, preferably 0 to 10% by weight, more preferably 0.5 to 5% by weight, based on the solid content of the emulsion polymer, of additional components, such as auxiliaries or residues of auxiliaries added during polymerization and / or subsequent processing, for example emulsifiers, initiators, buffers or molecular weight regulators as described below. In particular, the alkyl (meth)acrylate emulsion polymer may contain 0 to 15% by weight, preferably 0.001 to 10% by weight, more preferably 0.01 to 5% by weight, based on the solid content of the emulsion polymer, of molecular weight regulators, for example as described below.

[0085] Core-shell emulsion polymer

[0086] For example, the impact modifiers are based on two-phase emulsion polymers consisting of a soft elastomeric core and a hard shell, as described, for example, in EP 0 528 196, DE 38 42 796, DE 10 2005 062 687. In particular, the core-shell emulsion polymers are obtainable by a two-step emulsion polymerization in water, as described, for example, in DE-A 38 42 796. In a first step, the core particles are prepared by emulsion polymerization, and the shell is prepared by emulsion polymerization of a monomer mixture in the presence of the core particles.

[0087] Typically, the hard phase has a glass transition temperature T above 70°C. g The soft core has a glass transition temperature T of below -10°C. g and contains 50 to 99.5 wt % of acrylic acid C1-C 10 Alkyl ester and 0.5 to 5 wt % of a crosslinking monomer. In addition, the soft core may have a glass transition temperature T below -10°C. g And may contain 50 to 100 wt % of at least one conjugated diene, such as butadiene, based on the soft core.

[0088] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising (preferably consisting of):

[0089] A1) 10 to 95% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances:

[0090] A1.1) 50 to 99.5% by weight, based on A1, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate;

[0091] A1.2) 0.5 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and

[0092] A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and

[0093] B1) 5 to 90% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances:

[0094] B1.1) 80 to 100% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and

[0095] B1.2) 0 to 20% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, selected, for example, from C1-C6-alkyl acrylates, such as butyl acrylate or ethyl acrylate.

[0096] In another preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising (preferably consisting of):

[0097] A1) 50 to 90% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances:

[0098] A1.1) 90 to 100% by weight, based on A1, of at least one conjugated diene, preferably butadiene;

[0099] A1.2) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and

[0100] A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, for example at least one vinylaromatic monomer, preferably styrene and / or α-methylstyrene; and

[0101] B1) 10 to 50% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances:

[0102] B1.1) 70 to 90% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and

[0103] B1.2) 10 to 30% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, selected, for example, from vinylaromatic monomers, preferably styrene and / or α-methylstyrene.

[0104] Preferably, the degree of grafting of the core-shell emulsion polymer is at least 50% by weight, preferably from 50 to 60% by weight, based on the total solids content of the emulsion polymer.

[0105] Typically, the glass transition temperature T of a polymer or a phase of a multiphase emulsion polymer is g The glass transition temperature T can be determined in a known manner by differential scanning calorimetry (DSC). g It can also be calculated as an approximation using the Fox equation.

[0106] Core-Shell-Shell Emulsion Polymer

[0107] For example, impact modifiers are based on three-phase emulsion polymers, which consist of a hard core, for example of crosslinked methyl methacrylate, a polyol, for example of crosslinked acrylic acid C1-C1 10 The core-shell-shell emulsion polymers are generally prepared as described in EP 1 332 166 B1, WO 02 / 20634 and EP 0 522 351.

[0108] In particular, the poly(alkyl)methacrylate impact modifier may comprise a methacrylate / butadiene / styrene copolymer or an acrylate / methacrylate copolymer.

[0109] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell-shell emulsion polymer comprising (preferably consisting of):

[0110] A2) 5 to 40% by weight, based on the total emulsion polymer, of a rigid non-elastomeric core A2 having a glass transition temperature T above 50° C. g , which is composed of the following substances:

[0111] A2.1) 80 to 100% by weight, based on A2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate;

[0112] A2.2) 0 to 20% by weight, based on A2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and

[0113] A2.3) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups;

[0114] B2) 20 to 75% by weight, based on the total emulsion polymer, of a soft elastomeric intermediate shell B2 having a glass transition temperature T below 0° C. g , which is composed of the following substances:

[0115] B2.1) 45 to 99.5% by weight, based on B2, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate;

[0116] B2.2) 0.5 to 5% by weight, based on B2, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and

[0117] B2.3) 0 to 50% by weight, based on B2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, preferably a monomer having aromatic groups; and

[0118] C2) 15 to 60% by weight, based on the total emulsion polymer, of a hard shell C2 having a glass transition temperature T above 50° C. g , which is composed of the following substances:

[0119] C2.1) 80 to 100% by weight, preferably 90 to 100% by weight, based on C2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; and

[0120] C2.2) 0 to 20% by weight, preferably 0 to 10% by weight, based on C2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.

[0121] Preferably, at least 15% by weight, more preferably at least 25% by weight, of the hard outer shell C2 is covalently bonded to the soft elastomeric middle shell B2.

[0122] Preferably, the degree of grafting of the core-shell-shell emulsion polymer is at least 50% by weight, preferably from 70 to 99% by weight, based on the total solids content of the emulsion polymer.

[0123] Production method of poly(meth)acrylate impact modifier

[0124] Furthermore, the present invention relates to a process for producing the poly(meth)acrylate impact modifier of the present invention comprising at least one multiphase alkyl(meth)acrylate emulsion polymer, comprising the following steps:

[0125] (i) preparing at least one heterogeneous alkyl (meth)acrylate emulsion polymer by emulsion polymerization, in particular by sequential emulsion polymerization, wherein the heterogeneous alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex;

[0126] (ii) coagulation and dehydration, preferably mechanical dehydration, of the latex obtained in step (i), wherein the coagulation is performed by means of physical coagulation, wherein a dehydrated alkyl (meth)acrylate emulsion polymer is obtained, and wherein the dehydrated alkyl (meth)acrylate emulsion polymer contains less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg, of alkali metal ions, based on the solid content of the alkyl (meth)acrylate emulsion polymer, and wherein the molar ratio of alkali metal ions to polyvalent metal ions in the dehydrated alkyl (meth)acrylate emulsion polymer is less than or equal to 1.3, preferably less than or equal to 1.2,

[0127] Therein a coagulant comprising at least one salt of a polyvalent metal ion, preferably selected from the group consisting of alkaline earth metals, zinc and aluminum, is added to the emulsion polymer before and / or during coagulation.

[0128] The preferred embodiments as described above in connection with the impact modifier of the invention apply correspondingly to the method of the invention.

[0129] In particular, the poly(meth)acrylate impact modifier comprising or preferably consisting essentially of a heterogeneous alkyl(meth)acrylate emulsion polymer can be obtained as a dry polymer powder, in particular after dehydration and drying.

[0130] In particular, the poly(meth)acrylate impact modifier comprising or preferably consisting essentially of a multiphase alkyl(meth)acrylate emulsion polymer can be obtained in the form of polymer granules. For example, the polymer powder obtained after drying can be granulated, for example by means of generally known melt extrusion processes, optionally with the addition of one or more additives and / or one or more additional polymer components. Furthermore, it is possible to obtain the impact modifier in the form of polymer granules, wherein the coagulation and dehydration in step ii) are carried out by means of thermal shear coagulation in an extruder.

[0131] In a preferred embodiment, the coagulation is carried out by means of freeze coagulation, wherein the aqueous phase of the coagulated emulsion polymer is at least partially removed by mechanical dehydration, for example in a centrifugation step. Typically, the water content of the dehydrated emulsion polymer is in the range of 5 to 40% by weight, preferably 7 to 30% by weight, based on the dehydrated emulsion polymer. In a preferred embodiment, the coagulation and dehydration in step (ii) are carried out as described in WO 2015 / 074883.

[0132] Preferably, step (ii) may comprise a sintering step as described below. Furthermore, the process of the present invention may comprise one or more washing steps (iii) and / or one or more drying steps (iv) as described below.

[0133] In a preferred embodiment, the coagulation and dehydration in step ii) are carried out by extrusion. Typically, the latex obtained by emulsion polymerization is introduced into an extruder, which typically comprises a coagulation zone, a dehydration zone and a devolatilization zone. Preferably, the coagulation and dehydration by extrusion can be carried out as described in WO 02 / 18453, EP 0 683 028 or EP 0 187 715.

[0134] In another preferred embodiment, the coagulation and dehydration in step ii) is carried out by freeze coagulation. Preferably, the coagulation and dehydration by freeze coagulation can be carried out as described in WO 2015 / 074883.

[0135] Emulsion polymerization (step (i))

[0136] The process of the present invention comprises an emulsion polymerization step (i), wherein at least one heterogeneous alkyl (meth)acrylate polymer is prepared by emulsion polymerization, in particular by sequential emulsion polymerization, and the heterogeneous alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex.

[0137] The multiphase emulsion polymers are prepared in the usual manner by two-stage, three-stage or multistage emulsion polymerization in aqueous phase. Typically, the stages of the emulsion polymerization are carried out at temperatures of from 20 to 100°C, preferably from 60 to 90°C.

[0138] Typically, the core is made by emulsion polymerization in the first stage. Typically, the average particle size of the core is 50 to 150 nanometers (nm) for core-shell emulsion polymers and 100 to 300 nanometers (nm) for core-shell-shell emulsion polymers. Methods for adjusting the desired particle size are known to those skilled in the art. Advantageously, the control of particle size is carried out according to the seed latex method described in, for example, US2007 / 0123610 A1 and WO 2004 / 056893.

[0139] In the case of core-shell emulsion polymers, the hard outer phase is produced in a second polymerization stage after completion of the first polymerization stage in the presence of a soft core.

[0140] In the case of core-shell-shell emulsion polymers, the elastomeric mesophase is prepared in a second polymerization stage after the first polymerization stage in the presence of the core. Finally, in a third stage, after the second polymerization stage, the final rigid phase is produced in the same manner in the presence of the emulsion polymer of the second stage.

[0141] The emulsion polymerization is suitably carried out in the presence of an anionic emulsifier. Commonly known anionic emulsifiers are, for example, alkyl sulfates, alkyl sulfonates, alkyl sulfonic acids, aralkyl sulfonates, soaps of saturated or unsaturated fatty acids. Anionic emulsifiers selected from sulfonates, alkyl sulfosuccinates and alkoxylated and sulfated paraffins and mixtures thereof are preferably used.

[0142] Preferably, the emulsion polymer latex is polymerized by aqueous free radical emulsion polymerization. The reaction is usually initiated by a water-soluble or oil-soluble free radical polymerization initiator.

[0143] For example, suitable polymerization initiators are selected from inorganic or organic peroxides, such as dilauroyl peroxide, tert-butyl peroctanoate, tert-butyl perisononanoate, dicyclohexyl peroxydicarbonate, dibenzoyl peroxide and 2,2-bis(tert-butylperoxy)butane; azo compounds, such as 2,2'-azobis(isobutyronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile), and redox initiator systems. Examples of suitable redox systems are combinations of tertiary amines with peroxides or sodium metabisulfite and potassium, sodium or ammonium persulfates or preferably peroxides.

[0144] It is also preferred to carry out the polymerization using a mixture of various polymerization initiators of different half-lives (eg, dilauroyl peroxide and 2,2-bis(tert-butylperoxy)butane) to keep the flux of free radicals constant during the polymerization or at various polymerization temperatures.

[0145] The polymerization initiator is generally used in an amount of 0.01 to 2% by weight, based on the monomer mixture. Typically, the polymerization initiator is used in the range of 0.01 to 0.5% by weight, based on the aqueous emulsion polymerization mixture.

[0146] Preferably, alkali metal peroxodisulfate or ammonium peroxodisulfate is used as polymerization initiator, for example in amounts of 0.01 to 0.5% by weight, based on the aqueous phase of the polymerization mixture, wherein the polymerization is preferably initiated at temperatures of 20 to 100°C.

[0147] Preferably, a redox system is used as the polymerization initiator, for example 0.01 to 0.05 wt % of an organic hydroperoxide and 0.05 to 0.15 wt % of sodium hydroxymethanesulfinate (e.g. ), each based on the aqueous phase of the polymerization mixture, wherein the polymerization is preferably initiated at temperatures of 20° C. to 80° C.

[0148] The chain length of the polymer can be adjusted, in particular in the external hard phase, by polymerizing the monomer mixture in the presence of a molecular weight regulator. In particular, known mercaptans can be used for this purpose, such as n-butyl mercaptan, n-dodecyl mercaptan, 2-mercaptoethanol or 2-ethylhexyl thioglycolate or pentaerythritol tetramercaptoacetate. Typically, the amount of molecular weight regulator is 0.05 to 5% by weight, based on the monomer mixture, preferably 0.1 to 2% by weight, particularly preferably 0.2 to 1% by weight, based on the monomer mixture. Preferably, n-dodecyl mercaptan is used as a molecular weight regulator.

[0149] It is also possible to use salts, acids and bases in the emulsion polymerization, in particular for adjusting the pH or buffering the reaction mixture. For example, solutions of sulfuric acid, phosphoric acid, sodium hydroxide, potassium hydroxide, carbonates, bicarbonates, sulfates and / or sodium and potassium salts of phosphates (e.g. tetrasodium pyrophosphate) may be used. Typically, the pH of the emulsion polymer latex obtained in step (i) is in the range of 2 to 7, preferably 2.5 to 6.

[0150] Typically, the solid content of the emulsion polymer latex obtained in step (i) is in the range of 20 to 60 wt %, based on the total weight of the emulsion polymer latex. If necessary, the solid content may be adjusted.

[0151] Coagulation and mechanical dehydration (step (ii))

[0152] The method of the present invention comprises coagulation and dehydration in step (ii), preferably mechanical dehydration, wherein the latex obtained in step (i) is coagulated by means of physical coagulation, and the physical coagulation is preferably selected from shear coagulation, hot shear coagulation, spray drying, freeze coagulation and pressure coagulation, more preferably by means of freeze coagulation, shear coagulation or hot shear coagulation, and wherein a dehydrated (meth)acrylate alkyl ester emulsion polymer is obtained, which contains less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg of alkali metal ions based on the solid content of the (meth)acrylate emulsion polymer, and wherein the molar ratio of alkali metal ions to polyvalent metal ions in the dehydrated (meth)acrylate alkyl ester emulsion polymer is less than or equal to 1.3, preferably less than or equal to 1.2.

[0153] According to the present invention, "coagulation by physical means" or "physical coagulation" refers to agglomeration and precipitation of polymer particles in an emulsion polymer latex by applying physical methods, wherein the repulsive forces between the polymer particles are generally reduced which achieves separation and stabilization of the polymer particles in the latex. Typically, "chemical coagulation" refers to agglomeration and precipitation of polymer particles in an emulsion polymer latex by adding chemical agents (coagulants) which typically partially or completely achieve neutralization of the stabilizing charges located at the polymer particles.

[0154] According to the process for producing a poly(meth)acrylate impact modifier of the present invention, the coagulation is carried out by means of physical coagulation in combination with the addition of a coagulant before and / or during the coagulation (ie, by a combination of physical coagulation and chemical coagulation).

[0155] Physical coagulation of the emulsion polymer latex can be carried out by spray drying, freeze coagulation (described, for example, in WO 2015 / 07488) or by applying mechanical and / or thermal stress, in particular using a degassing extruder (described, for example, in WO 2002 / 18453, EP-A 0 979 162, EP-A 0 683 028).

[0156] According to the invention, a coagulant comprising at least one salt of a polyvalent metal ion preferably selected from alkaline earth metals, zinc and aluminum, more preferably selected from magnesium, calcium and aluminum, is added to the emulsion polymer before and / or during coagulation. In a preferred embodiment, at least one calcium salt is added as coagulant. Preferably, the coagulant is an aqueous solution of at least one salt of a polyvalent metal ion preferably selected from alkaline earth metals, zinc and aluminum, more preferably selected from magnesium, calcium and aluminum. Typically, the aqueous solution comprises 2 to 30% by weight, preferably 5 to 25% by weight, of the salt of the at least one polyvalent metal ion. Preferably, the aqueous solution of the at least one salt of the polyvalent metal ion is a true clear solution, in which the entire amount of the polyvalent metal ions is in solvated form.

[0157] Typically, the coagulant is an aqueous solution of at least one salt of a polyvalent metal ion having good solubility in water. Preferably, the salt of the polyvalent metal ion should have a solubility in water of 0.1 mol / l or more, preferably 0.5 mol / l or more, more preferably 1.0 mol / l or more, and also preferably 3.0 mol / l or more (e.g. at a temperature of 20 to 25°C, preferably at room temperature 23°C). In particular, the salt of the polyvalent metal ion is selected from water-soluble acetates, chlorides, hydroxides and / or sulfates, wherein water-soluble means that the solubility in water at room temperature 23°C is at least 0.1 mol / l, preferably at least 1.0 mol / l. For example, an aqueous solution of calcium acetate, calcium chloride, calcium hydroxide, magnesium sulfate, magnesium chloride, aluminum sulfate or a mixture thereof can be used as a coagulant.

[0158] In particular, the coagulant is selected to avoid the formation of less water-soluble metal salts or water-insoluble salts in the coagulant mixture.

[0159] Typically, the pH of the coagulation mixture during the coagulation step is in the range of 2 to 7, preferably 2.5 to 6.

[0160] Typically, the at least one salt of a polyvalent metal ion preferably selected from alkaline earth metals, zinc and aluminum is added in an amount in the range of 0.01 to 10 wt %, preferably 0.02 to 5 wt %, more preferably 0.03 to 3 wt %, based on the solid content of the polymer dispersion. In particular, the at least one salt of a polyvalent metal ion is added in the range of 0.01 to 2 moles based on the molar amount of the sum of the alkali metal ions in the emulsion polymer latex obtained in step (i). For example, 0.01 to 2 moles of alkaline earth metal ions are added to the emulsion polymer latex based on 1 mole of alkali metal ions.

[0161] In particular, the salt of the at least one polyvalent metal ion is selected from metal halides (such as chlorides), metal sulfates, metal phosphates (such as orthophosphates or pyrophosphates), metal hydroxides, organic acid metal salts (such as metal acetates, metal oxalates, metal citrates and metal formates). Preferably, the salt of the at least one polyvalent metal ion is selected from chlorides, sulfates and acetates. In addition, commonly known hydrates of the salts can be used.

[0162] For example, suitable alkaline earth metal salts are magnesium sulfate (such as kieserite (Mg[SO4]·H2O), Epsom salt pentahydrate (Mg[SO4]·5H2O), Epsom salt hexahydrate (Mg[SO4]·6H2O) and Epsom salt (Mg[SO4]·7H2O, Epsom salt)), magnesium chloride, calcium chloride, calcium hydroxide, calcium acetate, calcium formate, magnesium formate or mixtures thereof. Calcium acetate is particularly preferably used.

[0163] For example, suitable aluminum salts are aluminum sulfate (Al2(SO4)3), aluminum sulfate hydrate, aluminum chloride (AlCl3), aluminum chlorohydrate, aluminum chlorohydrate and polyaluminum chloride.

[0164] For example, suitable zinc salts are zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc sulfate hydrate (eg ZnSO4.7H2O) and zinc oxalate.

[0165] It is also possible to use a mixture of salts of two or more polyvalent metal ions as mentioned above. For example, it is possible to use a combination of at least an alkaline earth metal salt and at least one aluminum salt.

[0166] Typically, the coagulation may be carried out at a temperature ranging from 20 to 100°C; preferably from 30 to 80°C.

[0167] The dehydration of the coagulated latex can be carried out by mechanical dehydration (e.g. centrifugation and / or filtration) and / or by thermal dehydration (e.g. by evaporation of the aqueous phase of the emulsion polymer, e.g. via spray drying). In addition, it is possible to carry out the coagulation and dehydration of the emulsion polymer latex in one step, e.g. in the case of spray drying or in the case of coagulation and dehydration in a degassing extruder.

[0168] Preferably, the dehydration of the coagulated emulsion polymer is carried out by mechanical dehydration, for example by means of centrifugation, decantation or filtration. Preferably, the coagulated emulsion polymer is dehydrated by means of batch or continuous centrifugation. Typically the coagulated emulsion polymer is centrifuged for a period of 90 seconds to 10 minutes.

[0169] According to a further embodiment of the invention, the dewatering of the coagulated emulsion polymer is carried out by means of a degassing extruder, in particular in at least one dewatering zone of an extruder for shear or hot shear coagulation of emulsion polymers.

[0170] Typically, the dewatered emulsion polymer obtained in step (ii) has a water content less than or equal to 40% by weight, preferably in the range of 2 to 35% by weight, more preferably 5 to 20% by weight.

[0171] The water content of the multistage emulsion polymer after dehydration (also referred to as residual moisture content) is the water content expressed as a percentage by weight, based on the wet polymer obtained after dehydration. The water content is determined in particular with the aid of a suitable analytical device, such as a drying and weighing device, wherein the sample is dried until a constant weight of the sample is achieved within a defined period of time. For example, the water content of the emulsion polymer can be determined in a moisture analyzer, wherein the sample is dried at a temperature of 80 to 180° C. In particular, the water content can be determined using a Halogen Moisture Analyzer from Mettler Toledo at 160° C. until a constant weight is reached for 30 seconds.

[0172] Preferably, the dewatered alkyl (meth)acrylate emulsion polymer obtained in the dewatering step (ii) or after the optional washing step (iii) comprises 0 to 3.0 mmol / kg, preferably 0 to 2.5 mmol / kg, further preferably 0.0 to 2.0 mmol / kg, particularly preferably 0.01 to 3 mmol / kg, based on the solids content of the emulsion polymer, of alkali metal ions (e.g. sodium and / or potassium) and 0.5 to 20.0 mmol / kg, preferably 2.0 to 10.0 mmol / kg, more preferably 2.0 to 8.0 mmol / kg, based on the solids content of the emulsion polymer, of polyvalent metal ions preferably selected from alkaline earth metals (e.g. magnesium and / or calcium), zinc and aluminum.

[0173] Optional sintering

[0174] In particular, step (ii) of the process of the present invention comprises a sintering step after coagulation of the emulsion polymer and before dehydration.

[0175] Preferably, step (ii) may include a sintering step, wherein the condensed multistage alkyl (meth)acrylate emulsion polymer may be maintained at a temperature close to or below the glass transition temperature T of the outer phase / shell of the multistage alkyl (meth)acrylate emulsion polymer. g The sintering temperature (T s ). Preferably, the optional sintering step is carried out after agglomeration and before dehydration. In particular, the optional sintering step is carried out at a temperature T s ≥T g -50K, preferably T s ≥T g -30K, preferably T g -15K≤T s ≤T g Performed at +5K.

[0176] Preferably, after the coagulation of the emulsion polymer, the coagulation mixture is kept at a temperature (sintering temperature) in the range of 60° C. to 140° C., preferably 70° C. to 135° C., more preferably 75° C. to 130° C. In particular, the coagulated emulsion polymer is kept at the sintering temperature T2 for a period of 2 minutes to 24 hours, preferably 2 to 15 minutes, preferably 3 to 10 minutes, more preferably 5 to 10 minutes.

[0177] In a preferred embodiment, the coagulated emulsion polymer may be treated with steam during a sintering step after coagulation.

[0178] The method for producing the poly(meth)acrylate impact modifier may include one or both of the following optional steps:

[0179] (iii) optionally, washing of the dehydrated alkyl (meth)acrylate emulsion polymer;

[0180] (iv) optionally, drying of the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step ii) or iii).

[0181] Optional washing step (iii)

[0182] In a preferred embodiment, the mechanical dewatering of the emulsion polymer in step (ii) is followed by a washing step (iii), wherein the dewatered emulsion polymer is preferably treated with water or a mixture of water and a polar water-miscible organic solvent. The water or the mixture is preferably removed by filtration or centrifugation after this treatment. Preferably, in the downstream washing step (iii), an emulsion polymer having a water content of less than or equal to 40% by weight, preferably in the range of 2 to 35% by weight, more preferably in the range of 5 to 20% by weight, is obtained.

[0183] For example, the washing step (iii) may be performed by adding water or a mixture of water and a polar water-miscible organic solvent during centrifugation, in particular during continuous centrifugation.

[0184] Preferably, the dewatered emulsion polymer obtained after the optional washing step (iii) exhibits the amounts of alkali metal ions and polyvalent metal ions, such as alkaline earth metal ions, zinc ions or aluminium ions as described above for the dewatered emulsion polymer obtained after step (ii).

[0185] Optional drying step (iv)

[0186] The process of the present invention for producing a poly(meth)acrylate impact modifier may comprise one or more optional drying steps (iv).

[0187] For example, the dewatered emulsion polymer can be dried by means of a hot drying gas, for example air, or by means of a pneumatic dryer. Drying can be carried out, for example, in a cabinet dryer or other generally known drying apparatuses, such as a flash dryer or a fluidized bed dryer. Typically, the optional drying step (iv) is carried out at a temperature of 50 to 160° C., preferably 55 to 155° C., particularly preferably 60 to 150° C.

[0188] In another embodiment, the coagulated and dewatered emulsion polymer is dried in a degassing extruder, in particular in an additional degassing section of the extruder used for coagulation and dewatering.

[0189] Typically, the resulting dried emulsion polymer has a water content of less than 5%, preferably less than 2%, preferably in the range from 0.05 to 2% by weight, preferably from 0.1 to 1.5% by weight, particularly preferably from 0.1 to 1% by weight.

[0190] Preferably, the dry emulsion polymer obtained, for example as powder or granules, exhibits the same amount of alkali metal ions and polyvalent metal ions, such as alkaline earth metal ions, zinc ions and aluminium ions as the dewatered and optionally washed emulsion polymer obtained after step (ii) or (iii).

[0191] In a preferred embodiment of the invention, in step (ii), the coagulation is carried out by means of freeze coagulation and the mechanical dehydration of the coagulated emulsion polymer is carried out by means of centrifugation, wherein the water content of the dehydrated emulsion polymer is less than or equal to 40% by weight, based on the dehydrated emulsion polymer, and wherein the process comprises

[0192] (iii) optionally, washing the dehydrated alkyl (meth)acrylate emulsion polymer;

[0193] (iv) drying the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step ii) or iii), wherein the poly (meth)acrylate impact modifier is obtained as polymer powder.

[0194] In another preferred embodiment of the present invention, in step (ii), coagulation and mechanical dehydration are carried out by means of thermal shear coagulation, wherein the latex obtained in step (i) is introduced into an extruder line, which comprises at least one coagulation zone, at least one dehydration zone and at least one degassing zone, wherein the poly(meth)acrylate impact modifier is obtained as polymer particles.

[0195] Optional ion exchange step

[0196] The process of the invention for producing an impact modifier may preferably comprise at least one ion exchange step, wherein the latex obtained in step (i) is contacted with an ion exchange material. Preferably, the latex does not exhibit coagulation in the optional ion exchange step, and the latex obtained in the optional ion exchange step is processed in a subsequent coagulation step (ii) as described above.

[0197] Typically, the ion exchange material can be at least one cation exchange material (i.e. a material comprising anionic groups, which can be loaded with protons H+) and / or at least one anion exchange material (i.e. a material comprising cationic basic groups). Different ion exchange materials can be used as a mixture in a contact step with the emulsion polymer latex and / or used successively in two or more contact steps with the emulsion polymer latex. For example, it is possible to contact the latex obtained in step (i) with an anion exchange material in a first step, and then contact the latex with a cation exchange material in a second step. In addition, it is possible to use a mixed ion exchange material comprising anions and cation exchange groups.

[0198] Preferably, at least one cation exchange material is used to reduce the amount of alkali metal ions before coagulation in step (ii). In a preferred embodiment, the latex obtained in step (i) is contacted with at least one cation exchange material, more preferably a strong acid cation exchange material, especially in protonated form (H form) in step (ii). Suitable cation exchange materials contain at least one acidic group, such as a carboxylic acid group (-COOH) or a sulfonic acid group (-S(=O)2OH), preferably a strong acid group, such as a sulfonic acid group. In the case where the cation exchange material is not in protonated form, for example in Na form, the cation exchange material can be treated with an aqueous acid solution, such as hydrochloric acid or sulfuric acid, to obtain the protonated H form of the exchange material. A suitable example of a commercially available cation exchange material is manufactured by Dow Chemical Co. under the trade name / trademark MARATHONC, MONOSPHERE C-350, HCR-S / S, MARATHON MSC, MONOSPHERE 650C, HCR-W2, MSC-1, HGR NG(H) DR-G8, 88. MONOSPHERE 88, MONOSPHERE C-600B, MONOSPHERE M-31, MONOSPHERE DR-2030, M-31, G-26(H), 50W-X4, 50W-X8, 66 ion exchange resin; manufactured by Rohmand Haas under the trade name / trademark 131. 15. 16. 31. 33. 35. 36. 39. 40 70. FPC11, FPC22, FPC23 ion exchange resin; manufactured by Brotech Corp. under the trade name / trademark PFC150, C145, C150, C160, PFC100, C100 ion exchange resin; and Monoplus manufactured by Thermax Limited Corp. under the trade name / trademark TM S100 and T42 ion exchange resin. Other acidic cation exchange resins known to those skilled in the art may also be used. Preferably, Dow Chemical Marathon C.

[0199] The latex obtained in step (i) may be contacted with the at least one ion exchange material in any suitable manner. For example, the ion exchange step may be performed by dispersing the ion exchange material in the latex or in a column ion exchange step.

[0200] In addition, the method of the present invention may include the optional following steps:

[0201] (v) adding one or more additives to the multiphase alkyl (meth)acrylate emulsion polymer.

[0202] At each stage of the process for producing the poly(meth)acrylate impact modifier of the present invention, for example before or during the dehydration of the coagulated emulsion polymer, suitable conventional additives may be mixed in. These include dyes, pigments, stabilizers, lubricants, UV protectants, etc.

[0203] The optional additives can be selected from the commonly known additives and / or auxiliaries for plastic materials. For conventional auxiliaries and additives, reference is made, for example, to "Plastics Additives Handbook", Hans Zweifel 6th edition, Hanser Publ., Munich, 2009. For example, the at least one additive can be selected from fillers, reinforcing agents, dyes, pigments, lubricants or mold release agents, stabilizers (especially light and heat stabilizers), antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides, fungicides, fluorescent whitening agents and foaming agents.

[0204] For example, the impact modifier may contain 0 to 15 wt %, preferably 0 to 10 wt %, more preferably 0.5 to 5 wt %, of at least one additive as mentioned above, based on the solid content of the impact modifier.

[0205] Thermoplastic molding composition and method for producing the same

[0206] In another aspect, the present invention relates to a thermoplastic molding composition (hereinafter also referred to as molding composition), which comprises the poly(meth)acrylate impact modifier of the present invention and optionally at least one resin based on a thermoplastic (meth)acrylate polymer. For example, such an impact-modified poly(meth)acrylate molding composition is described in WO2004 / 056893.

[0207] In particular, the thermoplastic molding composition comprises (preferably consists of):

[0208] 1 to 100% by weight, preferably 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier as described above;

[0209] 0 to 99% by weight, preferably 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer, preferably poly(methyl methacrylate), and

[0210] 0 to 50% by weight, preferably 0 to 10% by weight, based on the total molding composition, of one or more additives, preferably two or more additives, for example selected from UV absorbers, UV stabilizers, heat stabilizers, antioxidants, lubricants, dyes and processing agents; and / or one or more additional polymer components.

[0211] In general, the thermoplastic (meth)acrylate polymers here preferably comprise (preferably consist of), in each case based on their total weight,

[0212] 50.0 to 100.0% by weight, preferably 60.0 to 100.0% by weight, particularly preferably 75.0 to 100.0% by weight, in particular 85.0 to 99.5% by weight, of alkyl methacrylate monomers (or repeating units) having 1 to 20, preferably 1 to 12, more preferably 1 to 8, in particular 1 to 4 carbon atoms in the alkyl group,

[0213] 0.0 to 40.0% by weight, preferably 0.0 to 25.0% by weight, in particular 0.1 to 15.0% by weight, of alkyl acrylate monomers (or repeating units) having 1 to 20, preferably 1 to 12, advantageously 1 to 8, in particular 1 to 4 carbon atoms in the alkyl group,

[0214] 0.0 to 30 wt%, preferably 0.0 to 8.0 wt% of styrene monomers (or repeating units).

[0215] In particular, the thermoplastic (meth)acrylate polymer comprises at least 50.0% by weight, advantageously at least 60.0% by weight, preferably at least 75.0% by weight and in particular at least 85.0% by weight of methyl methacrylate, based on its total weight.

[0216] For example, the molding composition may comprise one or more additives selected from dyes, pigments and crosslinked polymer beads and / or one or more additional polymer components.

[0217] In a preferred embodiment, the thermoplastic molding composition of the invention as described above comprises up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total thermoplastic molding composition, of at least one dye and / or pigment, for example selected from perinone dyes, quinophthalone dyes, anthraquinone dyes, azo dyes, inorganic pigments, phthalocyanine pigments and carbon black.

[0218] In addition, the thermoplastic molding composition of the present invention as described above may contain 0.01% to 50% by weight of at least one crosslinked polymer bead, preferably selected from crosslinked polymer beads having a different refractive index compared to the refractive index of the polymer matrix formed by the thermoplastic molding composition (scattering beads), based on the total thermoplastic molding composition. Suitable crosslinked polymer beads are described below.

[0219] Typically, the thermoplastic (meth)acrylate polymers have a number-average molar mass in the range of 1000 to 100 000 000 g / mol, preferably in the range of 10 000 to 1 000 000 g / mol, in particular in the range of 50 000 to 500 000 g / mol. The molar mass can be determined by gel permeation chromatography, for example with calibration based on polymethyl methacrylate.

[0220] The invention furthermore relates to a process for producing thermoplastic molding compositions, in which the components, usually in the form of their melt or in the form of powder or granules, are mixed and homogenized, for example in a single-screw or multi-screw extruder or on a roll mill.

[0221] In particular, the method for producing a thermoplastic molding composition comprises:

[0222] xi) mixing from 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier according to the invention as described above; from 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer; and optionally from 0 to 10% by weight of one or more additives and / or one or more additional polymer components; and

[0223] xii) melt compounding the mixture obtained in step xi) preferably at a temperature of 200 to 280°C.

[0224] Conventional additives can be mixed in at any processing stage suitable for this purpose. These include dyes, pigments, fillers, reinforcing fibers, lubricants, UV stabilizers, organic or inorganic scattering particles, etc.

[0225] Furthermore, the invention relates to mouldings or semi-finished products, such as foils, films or sheets, produced from the thermoplastic moulding compositions described above.

[0226] The thermoplastic molding composition can be used to produce any type of molded articles and semi-finished products, such as sheets, films, fiber foams, etc. The processing can be carried out using known thermoplastic processing methods, in particular by thermoforming, (co)-extrusion, injection molding, calendering, blow molding, compression molding, press sintering, deep drawing or sintering, preferably by injection molding.

[0227] Molded products or semi-finished products

[0228] The invention also relates to a moulding or semi-finished product made from the thermoplastic moulding composition according to the invention as described above.

[0229] For example, the molded article or semi-finished product may comprise the thermoplastic molding composition of the invention as described above and further one or more additives as described above and / or one or more further polymer components, which additives may be selected from dyes, pigments and crosslinked polymer beads, for example.

[0230] Preferably, the molded article or semi-finished product comprises up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total molded article or semi-finished product, of at least one additive, preferably selected from dyes, pigments, organic scattering particles (in particular crosslinked polymer beads as described below) and inorganic scattering particles.

[0231] Preferably, the molded article or semi-finished product contains up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total molded article or semi-finished product, of at least one dye and / or pigment, preferably selected from perinone dyes, quinophthalone dyes, anthraquinone dyes, azo dyes, inorganic pigments, phthalocyanine pigments and carbon black.

[0232] Preferably, the molded article or semi-finished product comprises 0.01% to 50% by weight, based on the total molded article or semi-finished product, of at least one organic or inorganic scattering particle, preferably selected from crosslinked polymer beads, more preferably selected from crosslinked polymer beads having a refractive index different from the refractive index of the polymer matrix formed from the thermoplastic molding composition (scattering beads).

[0233] In a preferred embodiment, the semi-finished product is a film or a sheet.

[0234] In a preferred embodiment, the molded article or semi-finished product is transparent. In particular, the molded article or semi-finished product has a haze value determined after storage in water at 80° C. for 4 hours to 24 hours of less than or equal to 30.0%, preferably less than or equal to 20.0%, more preferably less than or equal to 10%, in particular less than or equal to 6.0%, which is measured by means of a BYK Gardner Hazegard-plus haze meter in accordance with ASTM D1003-13 at a material thickness of 40 μm to 1000 μm. In particular, the molded article or semi-finished product has a haze value determined in accordance with ASTM D1003-13 at a material thickness of 1 mm after storage in water at 80° C. for 24 hours of less than or equal to 30%, preferably less than or equal to 25.0%, more preferably less than or equal to 20.0%.

[0235] In particular, the molded article or semi-finished product is produced by providing a thermoplastic molding composition as described above and adding at least one additive, in particular selected from dyes, pigments and crosslinked polymer beads as described above, and mixing the thermoplastic molding composition and the at least one additive, preferably by melt compounding, for example in the course of a film-forming process or an injection molding process.

[0236] Typically, the dyes and / or pigments can be added to the thermoplastic molding compositions of the invention as described above in the form of a coloring preparation, a liquid composition comprising the coloring preparation or a masterbatch.

[0237] In some embodiments of the present invention, the molding composition may contain organic or inorganic scattering particles dispersed in the polymer matrix. The low haze values ​​of the impact-modified thermoplastic molding composition of the present invention after hot water storage may also be advantageous in combination with scattering particles, since a more uniformly opaque and matte appearance can be obtained even after hot water storage. Although the choice of scattering particles is not particularly limited, they are generally selected in such a way that the refractive index of the scattering particles differs from the refractive index of the copolymer matrix by at least 0.01. The refractive index can be measured at the Na D line at 589 nm at 23 ° C as specified in standard ISO 489 (1999).

[0238] The scattering particles typically have an average particle diameter of 0.01 μm to 100.0 μm. The average particle diameter of the scattering particles - expressed as the so-called volume average d50-value (i.e. 50% by volume of the particles have a particle size below the specified average particle size) can be measured according to the laser diffraction measurement standard ISO 13320-1 (2009). Typically, the size of the scattering particles is determined by laser scattering using a Beckman Coulter LS13 320 laser diffraction particle size analyzer, for example at room temperature 23°C.

[0239] Inorganic scattering particles may include conventional inorganic opacifiers such as barium sulfate, calcium carbonate, titanium dioxide, or zinc oxide.

[0240] The organic scattering particles are usually spherical scattering beads composed of crosslinked polymer materials such as polyalkyl (meth)acrylates, silicones, polystyrene, etc. Preferably, at least 70%, especially at least 90%, based on the number of scattering beads, are spherical.

[0241] The preferred scattering beads composed of cross-linked polystyrene are available under the trademark SBX-4, SBX-6, SBX-8 and SBX-12 was purchased from Sekisui Plastics Co., Ltd.

[0242] Other particularly preferred spherical plastic particles for use as scattering agents include crosslinked silicones. Particularly preferred silicone scattering agents for use in the present invention can be used as 120 and 3120 was obtained from Momentive Performance Materials Inc. BRIEF DESCRIPTION OF THE DRAWINGS

[0243] exist Figure 1-7 The coagulants and auxiliary materials used are indicated in brackets, where CaAc2 is calcium acetate, CaCl2 is calcium chloride, CaOH2 is calcium hydroxide, MgAc2 is magnesium acetate, and MgSO4 is magnesium sulfate. Na2CO3 and NH3 represent sodium carbonate and ammonia, and CaHyp2 is calcium hypophosphite Ca(H2PO2)2.

[0244] Figure 1 The haze difference (Δhaze) of 1 mm pressed plaques made of core-shell emulsion polymers (EP1-4) processed by freeze coagulation (EP1-3) or hot shear coagulation (EP4) and dehydration before and after hot water storage at 80°C for 24 hours is shown as a function of the amount of sodium given in mmol / kg (impact modifier) ​​m Na changes.

[0245] Figure 2 The results show that the polymerization process consists of freezing coagulation and subsequent blending with PMMA as a blending component (w IM =36wt%, w PMMA =64 wt %)) before and after hot water storage at 80° C. for 24 h. The difference in haze (Δhaze) of 1 mm pressed plaques made from a core-shell-shell emulsion polymer (EP5) processed with 1% NH 2 O (EP5) as a function of the amount of sodium given in mmol / kg (impact modifier) ​​m Na changes.

[0246] Figure 3 The results show that the polymerization process is carried out by freezing coagulation and subsequent blending with PMMA as a blending component (w IM =33wt%, w PMMA =67 wt %)) before and after hot water storage at 80° C. for 24 h. The difference in haze (Δhaze) of 1 mm pressed plaques made from a core-shell-shell emulsion polymer (EP6) processed with 1% NH 2 O (EP6) as a function of the amount of sodium given in mmol / kg (impact modifier) ​​m Na changes.

[0247] Figure 4The haze difference (Δhaze) of 1 mm pressed plaques made from core-shell emulsion polymers (EP1-4) processed by freeze coagulation (EP1-3) or hot shear coagulation (EP4) and dehydration before and after hot water storage at 80°C for 24 hours is shown as a function of the molar ratio of sodium to calcium, magnesium, (calcium + magnesium) and aluminum, respectively, given as [mmol / kg (impact modifier)] / [mmol / kg (impact modifier)].

[0248] Figure 5 The steps of coagulation and dehydration by freezing and subsequent blending with PMMA as a blending component (w IM =36wt%, w PMMA =64 wt %) before and after hot water storage at 80°C for 24 h as a function of the molar ratio of sodium to calcium and magnesium, given as [mmol / kg (impact modifier)] / [mmol / kg (impact modifier)].

[0249] Figure 6 The steps of coagulation and dehydration by freezing and subsequent blending with PMMA as a blending component (w IM =33wt%, w PMMA =67 wt %) before and after hot water storage at 80°C for 24 h as a function of the molar ratio of sodium to calcium and magnesium, given as [mmol / kg (impact modifier)] / [mmol / kg (impact modifier)].

[0250] Figure 7 The reduction in polymer loss via wastewater during extrusion dewatering while processing the core-shell emulsion polymer EP4 (Examples 67 to 73) via hot shear coagulation is shown as a function of the molar ratio of sodium to calcium and magnesium, respectively, given as [mmol / kg (impact modifier)] / [mmol / kg (impact modifier)].

[0251] The reduction in polymer loss (in wt%) was calculated as 1-wP / wP,0, where wP,0 is the amount of polymer in the wastewater in Reference Example 67 (without addition of CaAc2), and wP is the amount of polymer in the wastewater in the corresponding Example.

[0252] The present invention is described in more detail by the following examples and claims. DETAILED DESCRIPTION

[0253] Example

[0254] General Description

[0255] Prepare and freeze coagulation have the emulsion polymer EP1, EP2 and EP3 (embodiment 1 to 40) of core-shell structure.Prepare and freeze coagulation have the emulsion polymer EP5 and EP6 (embodiment 41 to 61) of core-shell-shell structure.In addition, core-shell emulsion polymer EP1 is processed (embodiment 62 to 66) by heat and freeze coagulation and mechanical dehydration (centrifugation).Core-shell emulsion polymer EP4 (embodiment 67 to 73) and core-shell-shell emulsion polymer EP5 (embodiment 74 to 79) are processed by continuous hot shear coagulation and mechanical dehydration extrusion.Usually, core-shell-shell emulsion polymer is blended with PMMA subsequently.

[0256] Unless otherwise stated, different coagulants (coagulants), such as calcium salts, magnesium salts or aluminum salts, are added as mentioned before or after coagulation, in particular before coagulation.

[0257] The amount of metal ions was determined in the emulsion polymer as described below. In addition, samples were prepared and the haze values ​​were determined as described below. The results are summarized in the following table:

[0258] Table 2 (Examples 1 to 40) contains the results for the core-shell emulsion polymers EP1, EP2, EP3 processed by freeze coagulation and mechanical dehydration (centrifugation). Unless otherwise stated, the coagulant (coagulant) was added before freezing.

[0259] Table 4 (Examples 41 to 56) contains the results for core-shell-shell emulsion polymer EP5 processed by freeze coagulation and mechanical dehydration (centrifugation) and subsequently blended with PMMA (polymethyl methacrylate). Unless otherwise stated, the coagulant (coagulant) was added before freezing.

[0260] Table 5 (Examples 57 to 61) contains the results for core-shell-shell emulsion polymer EP6 processed by freeze coagulation and mechanical dehydration (centrifugation) and subsequently blended with PMMA. Unless otherwise stated, the coagulant (coagulant) was added before freezing.

[0261] Table 6 (Examples 62 to 66) contains the results for core-shell emulsion polymer EP4 processed by thermal and frozen coagulation and mechanical dehydration (centrifugation). Unless otherwise stated, the coagulant (coagulant) was added prior to freezing.

[0262] Table 7 (Examples 67 to 73) contains the results for core-shell emulsion polymer EP4 processed by sequential hot shear coagulation and mechanical dewatering extrusion. The examples are listed in the chronological order of the tests performed.

[0263] • Table 8 (Examples 74 to 79) contains the results for core-shell-shell emulsion polymer EP5 processed by sequential hot shear coagulation and mechanical dewatering extrusion and subsequently blended with PMMA. The examples are listed in the chronological order of the tests performed.

[0264] I. Examples 1-40 / Freeze-coagulation of emulsion polymers EP1, EP2 and EP3 (core-shell polymers)

[0265] Ia. Preparation of PMMA Latex Emulsion Polymers EP1, EP2 and EP3

[0266] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, an aqueous phase containing sodium hydroxymethyl sulfate, acetic acid, iron(II) sulfate (FeSO4) and an aqueous solution of the seed latex (having a solids content of 5% by weight) was placed.

[0267] At a temperature of 55° C. (container external temperature), emulsion I as described in Table 1 was added sequentially over a period of 20 minutes. After 10 minutes, emulsion II as described in Table 1 was added sequentially over a period of 2 hours. The reaction mixture was stirred for 60 minutes, cooled to 45° C. and filtered through VA steel (mesh size 90 μm). Emulsions I and II were each obtained by emulsifying the monomers and components as shown in Table 1.

[0268] The amounts used are summarized in Table 1 below.

[0269] Table 1. Emulsion polymerization of latex emulsion polymers EP1, EP2 and EP3 of Examples 1-40, all amounts are given in parts by weight

[0270]

[0271] SAS 30(Clariant):Sodium C14-17 alkyl secondary sulfonate

[0272] 1076(BASF):sterically hindered phenolic antioxidant

[0273] The resulting aqueous polymer dispersion had a solids content of 40-42% by weight.

[0274] Ion Exchange

[0275] According to Example 22, the emulsion polymer EP1 is subjected to an ion exchange step. 25 mL of a strongly acidic ion exchanger (Dowex Marathon C) provided in a protonated form (H form) is filled in a glass column with an inner diameter of 16 mm. The free volume above the ion exchanger bed is manually filled with an aqueous emulsion polymer EP1. After this, the emulsion is pumped through the column from top to bottom at a mass flow rate of 2.5 g / min. Samples are taken at the column outlet, and the sample is analyzed by AAS. The sodium content of the dispersion is less than 10 ppm. All embodiments are frozen, sintered and dehydrated as described in the following section lb.

[0276] Ib. Agglomeration, sintering and dehydration

[0277] To coagulate the emulsion polymers EP1, EP2, EP3 as described above, an aqueous solution of a metal salt (coagulant) was added at room temperature within 1-2 minutes while stirring (in the examples in which a coagulant was added). After the latex had completely coagulated, the dispersion was frozen at -18°C for 24 hours. According to the comparative example (without addition of coagulant), the emulsion polymers were frozen without addition of a metal salt solution. In comparative examples 18 and 19, different amounts of Ca(Ac)2 were added after freeze coagulation.

[0278] Thereafter the mixture was sintered at 80°C for 24 hours. The latex was cooled to room temperature and the particles were separated from the water by centrifugation at 1800 rpm. The centrifugation time was varied between 1.5 and 10 minutes to result in different residual water contents (w(H2O)) in the coagulated and dehydrated emulsion polymer.

[0279] The water content (w(H2O)) after centrifugation was determined using an electronic moisture analyzer (Sartorius MA45). The results are summarized in Table 2.

[0280] After centrifugation, the polymer was washed with deionized water (1 L) and centrifuged again. This procedure was performed three times and the resulting polymer powder was dried at 50°C for approximately 16-48 hours to obtain a final water content of <1%. Test specimens with a thickness of 1 mm were prepared from the dried material as described below.

[0281] The metal ion content (eg, sodium content, calcium content, and magnesium content) of the dehydrated and dried impact modifiers (emulsion polymers) of Examples 1 to 40 was determined as described below. The results are summarized in Table 2.

[0282] An aqueous solution of calcium acetate CaAc2, calcium hydroxide Ca(OH)2, calcium chloride CaCl2, magnesium sulfate MgSO4, magnesium acetate MgAc2, aluminum sulfate Al2(SO4)3, calcium hypophosphite Ca(H2PO2)2 and ammonia NH3 is used as a coagulant. For example, CaAc2 is used as an aqueous solution comprising 1 wt%, 10 wt% or 15 wt% CaAc2. The amount of the coagulant added to the emulsion polymer latex before or after coagulation is summarized in the table below and is given as a molar metal ion (e.g., Ca or Mg) based on the molar amount of sodium in the aqueous polymer dispersion. Based on the total aqueous polymer dispersion, the sodium content in the aqueous polymer dispersion is in the range of 0.012 to 0.05 wt%. The sodium content comes from the auxiliary agents added during the emulsion polymerization process, such as emulsifiers, reducing agents, initiators or buffers for pH regulation, and is calculated based on the amount of the auxiliary agents added during the polymerization process.

[0283] Ic. Preparation of Molding Compositions and Test Specimens

[0284] The dehydrated and dried impact modifiers (emulsion polymers) according to Examples 1-40 (based on emulsion polymers EP1, EP2, EP3) were compounded to obtain polymer particles. A single screw extruder with a diameter of 30 mm was used to melt and mix the polymers. The melt temperature was 235° C. The extrudate discharged from the extruder die was cooled in a water bath and pelletized.

[0285] Samples of 1 mm thickness and 5 cm diameter were prepared by hot pressing the pellets obtained as described above. The haze values ​​and transmittance of the samples were determined as described below. The results are summarized in the following Tables 2 and 2a (transmittance).

[0286]

[0287]

[0288]

[0289]

[0290]

[0291] Table 2a: Test results Transmittance

[0292]

[0293] *Embodiments of the present invention

[0294] It has been shown that if the amount of sodium is reduced to 3 mmol / kg or to less than 3 mmol / kg, preferably less than 2 mmol / kg and at the same time the molar ratio of alkali metal ions to multivalent ions (from the coagulant) is less than or equal to 1.3 mol / mol, an improved hot water storage stability is obtained with regard to haze values ​​and transmittance. This is also Figure 1 and 4 , in which the results according to Examples 1 to 40 are summarized.

[0295] II. Examples 41-61 - Freeze-coagulation of emulsion polymers EP5 and EP6 (core-shell-shell emulsion polymers)

[0296] IIa. Preparation of PMMA Latex Emulsion Polymer

[0297] Emulsion polymer EP5 was prepared as follows:

[0298] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, an aqueous phase containing acetic acid, iron (II) sulfate (FeSO4) and seeds (containing 10% by weight of PMMA) was placed. At a temperature of 52° C. (external temperature of the vessel), emulsion I as described in Table 3 was added over a period of 1 hour. In parallel, 0.69 g of sodium metabisulfite in 20 g of water was added (during the first 10 minutes). After 15 minutes, 1.94 g of sodium metabisulfite in 100 g of water was added in 10 minutes in parallel with the start of the addition of emulsion II as described in Table 3. Emulsion II (Table 3) was added over 2 hours, followed by a 50 minute interruption. Emulsion III as described in Table 3 was added simultaneously with 0.62 g of sodium metabisulfite in 50 g of water. The addition of sodium metabisulfite was completed within 10 minutes, emulsion III was completed after 1 hour. Thereafter the reaction mixture was stirred for 30 minutes, cooled to 35° C. and filtered through VA-steel (mesh size 100 μm).

[0299] Emulsion polymer EP6 was prepared as follows:

[0300] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, water, sodium carbonate and seeds (containing 10% by weight of PMMA) were placed. At a temperature of 83° C. (internal container temperature), emulsion I as described in Table 3 was added over a period of 90 minutes (addition 10 minutes, interruption 10 minutes, addition 80 minutes). After an interruption of 10 minutes, emulsion II as described in Table 3 was added. Emulsion II was added over 2 hours, then interrupted for 30-45 minutes. Emulsion III was added over 1 hour. Thereafter, the reaction mixture was stirred for 30 minutes, cooled to room temperature (approximately 30 minutes) and filtered through VA-steel (mesh size 100 μm).

[0301] Emulsions I, II and III were each obtained by emulsifying the monomers and components shown in Table 3.

[0302] Table 3. Emulsion polymerization of latex emulsion polymers EP5 and EP6 of Examples 41-61, all amounts given in grams

[0303] EP5 EP6 Water Phase water 1691.00 1711.00 Acetic acid 0.10 - <![CDATA[FeSO4]]> 0.0034 - seed 5.30 20.00 Sodium carbonate - 1.37 Emulsion I water 732.69 785.92 Sodium peroxodisulfate 0.51 0.70 Aerosol OT 75 4.67 5.60 Ethyl acrylate 29.40 47.60 Methyl Methacrylate 703.47 1140.02 Allyl methacrylate 2.21 2.38 Emulsion II water 628.65 542.39 Sodium peroxodisulfate 1.44 1.58 Aerosol OT 75 7.46 7.20 Butyl acrylate 1218.72 1234.71 Allyl methacrylate 19.53 22.95 Styrene 262.87 272.34 Emulsion III water 381.56 361.32 Sodium peroxodisulfate 0.44 0.70 Aerosol OT 75 1.34 1.08 Ethyl acrylate 38.35 26.52 Methyl Methacrylate 920.45 653.48 1-Dodecanethiol 3.36 -

[0304] Aerosol OT 75: an aqueous solution of dioctyl sodium sulfosuccinate (75%).

[0305] The resulting aqueous polymer dispersions had a solids content of 46-48% by weight (EP5) and 49-51% by weight (EP6).

[0306] IIb. Agglomeration, sintering and dehydration

[0307] Emulsion polymers EP5 and EP6 were processed as described above under 1b.

[0308] IIc. Preparation of Molding Compositions and Test Specimens

[0309] For compounding the dehydrated and dried impact modifier (emulsion polymer) according to Examples 41-61 (based on emulsion polymers EP5, EP6), a Haake Rheomix 5000 measuring mixer 30 was used. 42-45 grams of a polymer mixture consisting of polymethyl methacrylate PMMA_1 (copolymer of approximately 96% by weight of methyl methacrylate (MMA) and 4% by weight of methyl acrylate, with a weight average molecular weight of approximately Mw=110,000) and an impact modifier (amounts see table below) were slowly added to the mixing chamber. The amount of impact modifier (w(IM)) is shown in Tables 4 and 5. The polymer blend was mixed at a temperature of 220-230° C. (30 rpm) for 10 minutes. The resulting melt was removed from the chamber and crushed with pliers.

[0310] A sample with a thickness of 1 mm and a diameter of 5 cm was prepared by hot pressing the pellets obtained as described above. The haze value and transmittance of the sample were determined as described below. The results are summarized in Tables 4, 4a and 5 below.

[0311] Table 4 (Examples 41 to 56) and Table 5 (Examples 57 to 61) contain the results for core-shell-shell emulsion polymers EP5 and EP6 processed by freeze coagulation and mechanical dehydration (centrifugation) and subsequently blended with polymethyl methacrylate PMMA_1. Unless otherwise stated, the coagulant was added before freezing.

[0312] The water content in the emulsion polymer obtained after coagulation and dehydration is expressed as w(H2O). The amount of coagulant added is given as the amount of polyvalent metal cation (e.g. Ca(addition)) relative to the amount of sodium in the aqueous emulsion polymer composition, e.g. as mol Ca / mol Na The amount of impact modifier (emulsion polymer) in the molding compositions or in the test specimens for haze and transmittance is expressed as w(IM) given in % by weight. The amount of metal ions in the impact modifier (dried emulsion polymer) is given in mmol / kg (impact modifier).

[0313]

[0314]

[0315]

[0316] In Example 41, the coagulated emulsion polymer was isolated without a washing step and without centrifugation; the polymer was separated from the water only by filtration.

[0317] In Example 42, the coagulated emulsion polymer was isolated without a washing step and under centrifugation for 15 seconds. In Example 43, the coagulated emulsion polymer was isolated without a washing step and under centrifugation for 10 minutes.

[0318] Examples 52 to 54 were prepared according to the description of EP 5. Prior to coagulation, the pH of the dispersion was adjusted to pH 6.5-7 using sodium carbonate and (if necessary) ammonia solution. Coagulation, sintering and dehydration were carried out according to the described procedures.

[0319] Table 4a: Test results Transmittance

[0320]

[0321] It has been shown that if the amount of sodium is reduced to 3 mmol / kg or to less than 3 mmol / kg, preferably less than 2 mmol / kg and at the same time the molar ratio of alkali metal ions to multivalent ions (from the coagulant) is less than or equal to 1.3 mol / mol, an improved hot water storage stability is obtained with regard to haze values ​​and transmittance. This is also Figure 2 , 3 and 5, 6, where the results according to Examples 41 to 61 are summarized.

[0322] III. Examples 62-66 (Preparation of PMMA impact modifiers by heat and freeze coagulation) IIIa. Preparation of PMMA latex emulsion polymers

[0323] The core-shell emulsion polymer EP4 was formed as described above for EP1 to EP3 in two stages (impact modifier for PMMA molding compounds), wherein the following composition was processed:

[0324] Grade I: 98:2 butyl acrylate / allyl methacrylate

[0325] Stage II: Methyl methacrylate / butyl acrylate / dodecyl mercaptan in a ratio of 92:8:0.8

[0326] Mass ratio of I / II = 33.4 / 66.6

[0327] The mass ratio of polymer phase / water phase = 41 / 59

[0328] Average particle size: about 124nm

[0329] IIIb. Agglomeration, sintering and dehydration

[0330] Agglomeration was performed as follows:

[0331] Embodiment 62

[0332] 15kg of aqueous emulsion polymer product EP4 was loaded into a 25L stainless steel stirred vessel and heated while stirring with a paddle stirrer at 97rpm. During the heating phase, a pressure-resistant cylinder made of stainless steel was connected to the stirred vessel via a ball valve. The cylinder contained 62.6g of a 15 wt% MgSO4 aqueous solution and 62.6g of a 1 wt% ammonia solution. The cylinder was pressurized with nitrogen at a pressure higher than the internal pressure of the stirred vessel. When the internal temperature in the container reached 106°C, the ball valve was opened, and the cylinder contents were rapidly introduced into the dispersion by the pressure differential. The dispersion was then stirred for another 57 minutes under continuous heating, during which the internal temperature rose to 133°C. Thereafter, the contents of the container were cooled and the container was opened. The container contained a coagulated dispersion as well as an emulsified aqueous phase.

[0333] Embodiment 63

[0334] 15kg of aqueous emulsion polymer product EP4 was loaded into a 25L stainless steel stirred vessel and heated while stirring with a paddle stirrer at 111rpm. During the heating phase, a pressure-resistant cylinder made of stainless steel was connected to the stirred vessel via a ball valve. The cylinder contained 62.8g of a 15 wt% MgSO4 aqueous solution and 62.7g of a 1 wt% ammonia solution. The cylinder was pressurized with nitrogen at a pressure higher than the internal pressure of the stirred vessel. When the internal temperature in the container reached 152°C, the ball valve was opened, and the cylinder contents were rapidly introduced into the dispersion by the pressure differential. The dispersion was then stirred for another 82 minutes under continuous heating, during which the internal temperature rose to 153°C. Thereafter, the contents of the container were cooled and the container was opened. The container contained a coagulated dispersion and a milky aqueous phase.

[0335] Embodiment 64

[0336] 2004 g of aqueous emulsion polymer product EP4 was charged to a 2.4 L stainless steel stirred vessel and heated while stirring at 150 rpm with a 3-stage INTERMIG stirrer. During the heating phase, a pressure-resistant cylinder made of stainless steel was connected to the stirred vessel via a ball valve. The cylinder contained 8.4 g of a 15 wt % aqueous solution of MgSO4 and 8.4 g of a 1 wt % aqueous solution of ammonia. The cylinder was pressurized with nitrogen at a pressure higher than the internal pressure of the stirred vessel. When the internal temperature in the container reached 195° C., the ball valve was opened and the cylinder contents were rapidly introduced into the dispersion by the pressure differential. The dispersion was then stirred for another 10 minutes under continuous heating, during which the internal temperature rose to 209° C. Thereafter the contents of the container were cooled and the container was opened. The container contained a coagulated dispersion as well as a milky aqueous phase.

[0337] Embodiment 65

[0338] 2008g of aqueous emulsion polymer product EP4 was loaded into a 2.4L stainless steel stirred vessel and heated while stirring with a paddle stirrer at 150rpm. During the heating phase, a pressure-resistant cylinder made of stainless steel was connected to the stirred vessel via a ball valve. The cylinder contained 8.5g of a 15 wt% MgSO4 aqueous solution and 8.7g of a 1 wt% ammonia solution. The cylinder was pressurized with nitrogen at a pressure higher than the internal pressure of the stirred vessel. When the internal temperature in the container reached 223°C, the ball valve was opened, and the cylinder contents were rapidly introduced into the dispersion by the pressure differential. The dispersion was then stirred for another 10 minutes under continuous heating, during which the internal temperature rose to 224°C. Thereafter, the contents of the container were cooled and the container was opened. The container contained a coagulated dispersion and a milky aqueous phase.

[0339] Embodiment 66

[0340] 2000g of aqueous emulsion polymer product EP4 was loaded into a 2.4L stainless steel stirred vessel and heated while stirring at 150rpm with a paddle stirrer. During the heating phase, a pressure-resistant cylinder made of stainless steel was connected to the stirred vessel via a ball valve. The cylinder contained 8.95g of a 15 wt% MgSO4 aqueous solution. The cylinder was pressurized with nitrogen at a pressure higher than the internal pressure of the stirred vessel. When the internal temperature in the container reached 195°C, the ball valve was opened, and the cylinder contents were rapidly introduced into the dispersion by the pressure differential. The dispersion was then stirred for another 10 minutes under continuous heating, during which the internal temperature rose to 210°C. Thereafter, the contents of the container were cooled and the container was opened. The container contained a coagulated dispersion and a milky aqueous phase.

[0341] All examples were frozen, sintered and dehydrated as described in Section 1b.

[0342] IIIc. Preparation of Molding Compositions and Test Specimens

[0343] Dehydrated and dried impact modifiers (emulsion polymers) according to Examples 62-66 (based on emulsion polymer EP4) were compounded as described in Section 1c. Test specimens with a thickness of 1 mm and a diameter of 5 cm were prepared by hot pressing the pellets as described in Section 1c. The results are summarized in Table 6 below.

[0344]

[0345] IV. Examples 67 to 73 (Preparation of PMMA Impact Modifier Using Thermal Shear Coagulation)

[0346] IVa. Preparation of PMMA latex emulsion polymer

[0347] The core-shell emulsion polymer EP4 as described above (Section IIIa.) was used.

[0348] IVb. Agglomeration, sintering and dehydration

[0349] Before shear coagulation, different amounts of calcium acetate (CaAc2) were added to the emulsion polymer latex EP4 in the form of an aqueous solution (1 wt%, 10 wt% or 15 wt%). Calcium acetate (CaAc2) was added in an amount of 0.1 to 2 mol Ca based on the molar amount of sodium in the aqueous polymer dispersion (see Table 7, Ca (addition)). The amount of sodium in the aqueous dispersion was about 0.013 wt% based on the aqueous dispersion. The sodium content comes from the additives added during the emulsion polymerization process, such as emulsifiers, reducing agents, initiators or buffers for pH adjustment, and is calculated based on the amount of the additives added during the polymerization process.

[0350] The latex is pumped into the barrel of a counter-rotating twin-screw extruder (zone 1). The coagulation zone is divided into several main zones, starting with the first zone where the dispersion is fed into the extruder. The designated temperature of the heat jacket of the coagulation zone in the extruder is in the range of 150 to 210°C. The last zone is followed by a dewatering zone where the polymer melt is separated.

[0351] The collection tank for the separated water is maintained at a pressure of at least 28 bar via a pipeline. A water stream, which typically contains 8-10% polymer, is discharged via a valve. The feed flow to the degassing extruder is regulated by a valve to maintain a melt pressure of 40-60 bar.

[0352] In the degassing extruder, residual amounts of volatile constituents are separated from the polymer.The extruded or pelletized material discharged at the pelletizing nozzle has a residual moisture content of less than 5% by weight.

[0353] The polymer concentration in the water collected in the dehydration zone was analyzed with an electronic moisture analyzer HE53 from Mettler Toledo heated to 160° C. The results are given as a % reduction in polymer loss based on reference example 67 (without addition of CaAc2) (see Table 7 below). The reduction in polymer loss (Red. Loss) given in wt% was calculated:

[0354] Red.Loss (in wt%) = 1-w P,A / w P,A,0

[0355] where w P,A,0 is the amount of polymer in the wastewater of Reference Example 43 (without addition of CaAc2), and w P,A is the amount of polymer in the wastewater in the corresponding example.

[0356] IVc. Preparation of Molding Compositions and Test Specimens

[0357] Test specimens of 1 mm thickness and 5 cm diameter were prepared by hot pressing of the pellets obtained after the extrusion process.The haze of the test specimens before and after hot water storage and the amount of sodium and calcium in the dried emulsion polymer were determined as described below.

[0358] The results are summarized in Table 7, where the examples are given in chronological order. First, the emulsion polymer latex EP4 without the addition of CaAc2 was fed into the extruder, followed by the emulsion polymer latex A4 to which 10 wt % and 15 wt % (in this order) of the CaAc2 solution were added. Thereafter, the emulsion polymer latex EP4 without the addition of CaAc2 was fed. Samples were taken after the stabilization process was reached.

[0359] It has been shown that improved hot water storage stability is obtained if the amount of sodium is reduced to 3 mmol / kg or to less than 3 mmol / kg and at the same time the molar ratio of alkali metal ions to multivalent ions (from the coagulant) is less than or equal to 1.3 mol / mol. This is also Figure 7 , in which the results according to Examples 67 to 73 are summarized.

[0360] It has been shown that when the molar ratio of sodium to calcium is less than 1.3, the reduction in polymer loss (Red. Loss (in wt%) see above) increases significantly to about 90%. In particular, these favorable results are obtained when the amount of sodium in the emulsion polymer is less than 3 mmol / kg and the amount of calcium is greater than 2 mmol / kg.

[0361]

[0362] V. Examples 74 to 79 (Preparation of PMMA Impact Modifier Using Thermal Shear Coagulation)

[0363] Preparation of Va.PMMA Latex Emulsion Polymer

[0364] Core-shell emulsion polymer EP5 was prepared as described above (Section IIa).

[0365] Vb. Agglomeration, sintering and dehydration

[0366] Coagulation and dehydration of emulsion polymer EP5 were performed as described above for Examples 67 to 73 (Section IVb.). Emulsion polymer EP5 was processed by thermal shear coagulation and mechanical dehydration extrusion and subsequently blended with polymethyl methacrylate PMMA_1.

[0367] Vc. Preparation of Molding Compositions and Test Specimens

[0368] Test specimens of 1 mm thickness and 5 cm diameter were prepared by hot pressing of the pellets obtained after the extrusion process as described above for Examples 67 to 73 (Section IVc.). The haze of the test specimens before and after hot water storage and the amount of sodium and calcium in the dried emulsion polymer were determined as described below. The results are summarized in Table 8, where the examples are given in chronological order.

[0369]

[0370] VI. Test methods

[0371] VIa. Hot water mist

[0372] The test specimen (obtained by hot pressing, having a thickness of 1 mm and a diameter of 5 cm) was stored in deionized water at 80° C. for 24 hours. The haze value was measured before and after the hot water storage using a haze meter BYK Gardner haze-gard i according to ASTM D1003-13.

[0373] These specimens prepared as described above were tested at 23°C using a BYK Gardner haze-gard i haze meter according to ASTM D1003-13 in the original state ("before haze") and after hot water storage in deionized water at 80°C for 24 hours. It should be noted that materials with haze values ​​greater than 30% are considered "diffuse" according to ASTM D1003-13 and should be tested according to Practice for Goniometric Optical Scatter Measurements (E2387). Since the focus of the current study was on transparent materials with haze values ​​less than 30%, haze values ​​greater than 30% are reported for the purpose of illustrating the trend.

[0374] These haze values ​​and the difference (haze / Δ) between the haze values ​​before and after hot water storage (haze / 24 h - haze / 0 h) are summarized in the above table.

[0375] The transmittance (given in %) before and after hot water storage was determined accordingly in accordance with ASTM D1003-13.

[0376] VIb. Metal ion content

[0377] To determine the metal ion content (eg Na and Ca), microwave-assisted digestion of the dried emulsion polymer was performed with nitric acid. Thereafter the content of the relevant ions was determined by atomic absorption spectroscopy.

[0378] VIc. Water content

[0379] If not defined otherwise, the water content (residual water) was determined using an electronic moisture analyzer (Sartorius MA45) heated to 85° C. The reduction in polymer losses was determined as described above: Section IVb.—Coagulation, Sintering and Dehydration.

Claims

1. A poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer, wherein the poly(meth)acrylate impact modifier comprises at least one multivalent metal ion and less than or equal to 3.0 mmol / kg of alkali metal ions, based on the solid content of the impact modifier, and wherein the molar ratio of alkali metal ions to multivalent metal ions is less than or equal to 1.

3.

2. The poly(meth)acrylate impact modifier according to claim 1, characterized in that The molar ratio of the polyvalent metal ions to the alkali metal ions is greater than or equal to 0.8, preferably greater than or equal to 0.

9.

3. The poly(meth)acrylate impact modifier according to claim 1 or 2, characterized in that: The poly(meth)acrylate impact modifier comprises greater than or equal to 0.5 mmol / kg of multivalent metal ions based on the solid content of the impact modifier.

4. The poly(meth)acrylate impact modifier according to any one of claims 1 to 3, characterized in that The poly(meth)acrylate impact modifier contains 0 to 3.0 mmol / kg of alkali metal ions based on the solid content of the impact modifier and 0.5 to 20.0 mmol / kg of polyvalent metal ions based on the solid content of the impact modifier.

5. The poly(meth)acrylate impact modifier according to any one of claims 1 to 4, characterized in that The alkali metal ions are selected from sodium and potassium, and the polyvalent metal ions are selected from alkaline earth metals, zinc, calcium, magnesium and aluminum ions.

6. The poly(meth)acrylate impact modifier according to any one of claims 1 to 5, characterized in that The heterophasic alkyl (meth)acrylate emulsion polymer is obtained by emulsion polymerization and comprises a core and at least one, preferably one or two shells.

7. The poly(meth)acrylate impact modifier according to any one of claims 1 to 6, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer comprises: at least 10% by weight, preferably at least 20% by weight, of at least one C1-C10 alkyl methacrylate; 5 to 80% by weight, preferably 20 to 80% by weight, of at least one C1-C10 alkyl acrylate or at least one conjugated diene; 0 to 2 wt. %, preferably 0.1 to 2 wt. %, of at least one crosslinking monomer; 0 to 15 wt. %, preferably 0.5 to 10 wt. % of optional additional monomers, preferably vinyl aromatic monomers.

8. The poly(meth)acrylate impact modifier according to any one of claims 1 to 7, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising: A1) 10 to 95% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances: A1.1) 50 to 99.5% by weight, based on A1, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate; A1.2) 0.5 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and B1) 5 to 90% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances: B1.1) 80 to 100% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and B1.2) 0 to 20% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.

9. The poly(meth)acrylate impact modifier according to any one of claims 1 to 7, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer is a core-shell-shell emulsion polymer comprising: A2) 5 to 40% by weight, based on the total emulsion polymer, of a rigid non-elastomeric core A2 having a glass transition temperature T above 50° C. g , which is composed of the following substances: A2.1) 80 to 100% by weight, based on A2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; A2.2) 0 to 20% by weight, based on A2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and A2.3) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; B2) 20 to 75% by weight, based on the total emulsion polymer, of a soft elastomeric intermediate shell B2 having a glass transition temperature T below 0° C. g , which is composed of the following substances: B2.1) 45 to 99.5% by weight, based on B2, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate; B2.2) 0.5 to 5% by weight, based on B2, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and B2.3) 0 to 50% by weight, based on B2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, preferably a monomer having aromatic groups; and C2) 15 to 60% by weight, based on the total emulsion polymer, of a hard shell C2 having a glass transition temperature T above 50° C. g , which is composed of the following substances: C2.1) 80 to 100% by weight, preferably 90 to 100% by weight, based on C2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; and C2.2) 0 to 20% by weight, preferably 0 to 10% by weight, based on C2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.

10. A process for producing a poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer according to any one of claims 1 to 9, comprising the following steps: (i) preparing at least one multiphase alkyl (meth)acrylate emulsion polymer by emulsion polymerization, wherein the multiphase alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex; (ii) coagulation and dehydration of the latex obtained in step (i), preferably mechanical dehydration, wherein the coagulation is performed by means of physical coagulation, wherein a dehydrated alkyl (meth)acrylate emulsion polymer is obtained, and wherein the dehydrated alkyl (meth)acrylate emulsion polymer contains less than or equal to 3.0 mmol / kg, preferably less than or equal to 2.5 mmol / kg, of alkali metal ions, based on the solid content of the alkyl (meth)acrylate emulsion polymer, and wherein the molar ratio of alkali metal ions to polyvalent metal ions in the dehydrated alkyl (meth)acrylate emulsion polymer is less than or equal to 1.3, preferably less than or equal to 1.2, Therein a coagulant comprising at least one salt of a multivalent metal ion is added to the emulsion polymer before and / or during coagulation.

11. The method according to claim 10, characterized in that The dehydrated alkyl (meth)acrylate emulsion polymer obtained in step (ii) contains 0 to 3.0 mmol / kg of alkali metal ions based on the solid content of the emulsion polymer and 0.5 to 20.0 mmol / kg of polyvalent metal ions based on the solid content of the emulsion polymer.

12. The method according to claim 10 or 11, characterized in that: The coagulant is an aqueous solution of at least one salt of a multivalent metal ion selected from alkaline earth metals, zinc, calcium, magnesium, and aluminum.

13. The method according to any one of claims 10 to 12, characterized in that: In step (ii), the coagulation is carried out by means of freeze coagulation and the mechanical dehydration of the coagulated emulsion polymer is carried out by means of centrifugation, wherein the water content of the dehydrated emulsion polymer is in the range of 5 to 40% by weight, preferably 7 to 30% by weight, based on the dehydrated emulsion polymer, and wherein the process comprises (iii) optionally, washing the dehydrated alkyl (meth)acrylate emulsion polymer; (iv) drying the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step ii) or iii), wherein the poly (meth)acrylate impact modifier is obtained as polymer powder.

14. The method according to any one of claims 10 to 12, characterized in that: In step (ii), the coagulation and the mechanical dehydration are carried out by means of thermal shear coagulation, wherein the latex obtained in step (i) is introduced into an extruder line comprising at least one coagulation zone, at least one dehydration zone and at least one degassing zone, wherein the poly(meth)acrylate impact modifier is obtained as polymer particles.

15. A thermoplastic molding composition comprising: 1 to 100% by weight, preferably 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier according to any of claims 1 to 9; 0 to 99% by weight, preferably 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer, preferably poly(methyl methacrylate), and 0 to 50% by weight, preferably 0 to 10% by weight, based on the total molding composition, of one or more additives and / or one or more additional polymer components.

16. A method for producing a thermoplastic molding composition according to claim 15, comprising: xi) mixing from 1 to 100% by weight, preferably from 5 to 100% by weight, based on the total thermoplastic molding composition, of at least one poly(meth)acrylate impact modifier according to any of claims 1 to 9; from 0 to 99% by weight, preferably from 0 to 95% by weight, based on the total thermoplastic molding composition, of at least one thermoplastic (meth)acrylate polymer; and optionally from 0 to 50% by weight, preferably from 0 to 10% by weight, of one or more additives and / or one or more additional polymer components; and xii) melt compounding the mixture obtained in step xi).

17. A molded article or semi-finished product made from the thermoplastic molding composition according to claim 15.

18. The molded article or semi-finished product according to claim 17, characterized in that The molded product or semi-finished product comprises: Up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total molding or semi-finished product, of at least one additive selected from dyes, pigments, organic scattering particles and inorganic scattering particles.

19. The molded article or semi-finished product according to claim 17 or 18, characterized in that The molded article or semi-finished product has a haze value measured at a material thickness of 1 mm according to ASTM D1003-13 after water storage at 80° C. for 24 hours of less than or equal to 25.0%, preferably less than or equal to 20.0%.